Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Anatomy of the Middle and Late Miocene phase of Lake Megafazzan, central Sahara, southern Libya: lake margin deposits and environmental controls - Mark W. Hounslow; Nick Drake; Mustafa J. Salem; Simon J. Armitage; Helena E. White; Ahmed S. El-Hawat (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Shoulder Kinematic and Muscle Activity Compensations to Scapular Stabilizer Weakness: An Optimal Control Framework - Matthew S. Russell; Daanish M. Mulla; Peter J. Keir; Edward K. Chadwick; Dimitra Blana; Janessa D. M. Drake; Jaclyn N. Chopp-Hurley (Annals of Biomedical Engineering, 2026)
Purpose Shoulder kinematic and muscular redundancy promotes considerable variability, obscuring possible insights into neuromuscular control and compensation mechanisms for muscle weakness or fatigue. The current study harnessed recent advancements in optimal control formulations for computational musculoskeletal models to determine potential neuromuscular control strategies to compensate for isolated muscle weakness. Methods A computational shoulder model characterized by independent clavicular, scapular, and humeral kinematics and 138 muscle elements was used. Optimal control-predicted thoracohumeral elevation kinematics were validated against published empirical kinematics. Force-generating capacity of the upper trapezius, middle trapezius, and lower trapezius, and serratus anterior were individually limited to 75%, 50%, and 25% maximal capacity to generate subsequent optimal control predictions of scapulothoracic kinematic changes associated with muscle weakness. Combined limited maximal force-generating capacity of lower trapezius and serratus anterior was also explored. Results Model-predicted scapulothoracic kinematics showed good agreement with reference data, yet some significant differences were identified below 55° thoracohumeral elevation. Fatigue-mediated kinematic changes were most apparent during sagittal plane elevation. Serratus anterior weakness displayed the largest scapulothoracic kinematic changes at all thresholds of limited force-generating capacity. It also prompted the largest compensatory muscle activity changes from other shoulder muscles, while upper trapezius weakness prompted very little compensatory changes in muscle activity. Conclusion Optimal control simulations were used to identify potential compensation mechanisms for shoulder muscle weakness and predict their effects on scapular kinematics. Findings suggest that thoracohumeral elevation in the scapular plane displayed less trapezius coactivity, both when ‘weakened’ and ‘unweakened.’ Thus, scapular plane tasks may isolate serratus anterior, while frontal plane tasks may achieve more balanced coactivation.

A practical, low-cost floating flux chamber for measuring greenhouse gas emissions from small urban waterbodies - Bryn E. Reynolds; Cole J. C. Van De Ven; Evan Heyes; Jennifer Drake (Environmental Monitoring and Assessment, 2026)

Investigation of a novel assay for the proteomic screening of the secretory and excretory products of individual salmon lice Lepeophtheirus salmonis - Alexander Dindial; James E. Bron; Michael McGowan; Ava Drake; Kevin McLean; Dorota Androscuk; William Roy; Andre Van; Diego Robledo; Richard Paley; Claire Joiner; Mark D. Fast; et al. (Veterinary Parasitology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The combined effects of elevated within-group aggression and intergroup threat on dwarf mongoose behaviour - Josh J. Arbon; Amy Morris-Drake; Julie M. Kern; Andrew N. Radford (Animal Behaviour, 2026)

Development of a Stereolithography 3D Printing-Based Micropatterning Method to Study Endothelial-to-Mesenchymal Transition Mechanobiology - Karina Bender; Sarah Chesley; Jay Lesny Drake; Megan Ho; Emily Lin; Kathryn Saxton; Ninava Sharma; Christina K. Tripsas; Qian Li; Jeffrey J. Hsu (Annals of Biomedical Engineering, 2026)
Endothelial-to-mesenchymal transition (EndMT) is the process of endothelial cells undergoing molecular changes that shift their phenotype from that of endothelial cells to that of mesenchymal-like cells. It is a crucial developmental process that has been implicated in various physiological and pathological conditions. EndMT has gained attention as a potential therapeutic target for cardiovascular disease processes, including atherosclerosis, myocardial fibrosis, and vascular calcification. In addition to the assessment of endothelial and mesenchymal markers, the behavioral mechanics of endothelial cells, such as migration and invasion, are often used to identify endothelial cells that have undergone EndMT. However, whether cell chirality may be another mechanobiological marker of EndMT remains unclear. In this study, we aimed to develop an accessible micropatterning platform and created a stereolithography (SLA) 3D printing-based polydimethylsiloxane (PDMS) protein-stamp fabrication platform to create customized patterns of ECM proteins to study endothelial cell chirality during EndMT. Human aortic endothelial cells (HAECs) were treated with the inflammatory cytokine tumor necrosis factor-α (TNF-α), which resulted in the downregulation of the endothelial marker ENOS3 and the upregulation of the mesenchymal markers N-cadherin and transgelin, supporting the induction of EndMT. HAECs were seeded onto fibronectin stripe micropatterns, and cell chirality was measured using custom cell-profiling software. HAECs treated with TNF-α exhibited a shift in cell orientation by approximately 18°, supporting altered cell chirality during TNF-α-induced EndMT. Our work innovates novel methods of studying EndMT by developing a flexible and cost-effective protein-stamp fabrication and image analysis pipeline. This pipeline can be used by researchers to study the endothelial cell chirality in response to EndMT induction.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Assessing the intensity of Late Quaternary humid phases in the Nefud Desert, northern Arabia - Richard Clark‐Wilson; Simon J. Armitage; Ian Candy; Paul S. Breeze; Nick A. Drake; Huw S. Groucutt; Abdullah M. Alsharekh; Faisal Al‐Jibreen; Michael D. Petraglia; David B. Ryves (Journal of Quaternary Science, 2026)
The climate history of the major dryland zones of the world, such as the Saharo–Arabian Desert belt, plays a key role in the dispersal of early humans through these intermittently inhospitable regions. Here, we assess the relative intensity of Late Quaternary humid phases in northern Arabia through lithological, geochemical, palaeoecological and geochronological analysis of three sediment sequences in the Nefud Desert. Two sequences are marl beds that accumulated in perennial, groundwater‐fed lake systems during two distinct humid phases that occurred in MIS 5e and MIS 5a. The third records sediment accumulation within an ephemeral lake system during the terminal Pleistocene/early Holocene. The altitude of the two MIS 5 deposits indicates that the water table must have reached altitudes of >929 m ASL (MIS 5e) and >922 m ASL (MIS 5a). In contrast, the sedimentary characteristics of the early Holocene sequence imply that, during this interval, the water table was

Latest Tortonian to early Pliocene interdune lake systems, southern Libya: Implications for the hydrology of the central Sahara - Mark W. Hounslow; Helena E. White; Nick Drake; Vassil Karloukovski; Sue J. McLaren; Mustafa J. Salem; Ahmed S. El-Hawat; Osama Hlal (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Late Quaternary inundation and desiccation of Megalake Chad traced in dust records from the Equatorial Atlantic Ocean - Anya J. Crocker; Christopher W. Kinsley; Amy M. Jewell; Paul S. Breeze; Nicholas A. Drake; David McGee; Charles S. Bristow; Katie Manning; Claudia Di Biagio; Paola Formenti; William R.C. Burton; Annie L. Murray; et al. (Quaternary Science Reviews, 2025)

Triple oxygen isotopes in eggshell carbonate as a proxy of late Cenozoic CO2 and primary productivity - Vincent J. Hare; Drake A. Yarian; J. Tyler Faith; Chris Harris; Julia A. Lee-Thorp; Benjamin H. Passey; Kathryn G. Sokolowski; Loïc Ségalen (Geochimica et Cosmochimica Acta, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Effects of burning on vegetation, soil physicochemistry and prokaryotic microbial communities in surface and subsurface peat - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Science of The Total Environment, 2024)

Patterns in tree squirrel co-occurrence vary with responses to local land cover in US cities - Rachel N. Larson; Heather A. Sander; Mason Fidino; Julia L. Angstmann; Sheryl Hayes Hursh; Seth B. Magle; Katrina Moore; Carmen M. Salsbury; Theodore Stankowich; Katherine Tombs; Lauren Barczak; Alyssa M. Davidge; et al. (Urban Ecosystems, 2024)

Trace element partitioning between natural barite and deep anoxic groundwaters: Implications for radionuclide retention in host rocks of nuclear waste repositories - Ferdinand Kirchner; Martin Kutzschbach; Henrik Drake; Vanessa Fichtner; Piotr M. Kowalski; Stefan Rudin; Martin J. Whitehouse; Mikael Tillberg; Thomas Neumann (Applied Geochemistry, 2024)

Effects of fruit novelty on feeding preference in four globally invasive frugivorous birds - Samuel B. Case; Kapua Kawelo; Josephine Hoh; Dylan O’hearn; Jinelle H. Sperry; Jeffrey T. Foster; Donald R. Drake; Jeferson Vizentin-Bugoni; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2024)

Reply to comment on: Carbonaceous matter in ∼3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Changes in nitrogen functional genes and microbial populations in soil profiles of a peatland under different burning regimes - Shaun M. Allingham; Samantha J. Drake; Andrew Ramsey; Chris D. Field; Felix C. Nwaishi; David R. Elliott (Applied Soil Ecology, 2024)

A Review on the State of the Art in Frugivory and Seed Dispersal on Islands and the Implications of Global Change - Manuel Nogales; Kim R. McConkey; Tomás A. Carlo; Debra M. Wotton; Peter J. Bellingham; Anna Traveset; Aarón González-Castro; Ruben Heleno; Kenta Watanabe; Haruko Ando; Haldre Rogers; Julia H. Heinen; et al. (The Botanical Review, 2024)
We provide an overview of the current state of knowledge of island frugivory and seed dispersal and identify knowledge gaps that are important for fundamental research on—and applied conservation of—island ecosystems. We conducted a systematic literature search of frugivory and seed dispersal on islands, omitting large, continental islands. This revealed a total of 448 studies, most (75%) published during the last two decades, especially after 2010. Nearly 65% of them were focused on eight archipelagos. There is a paucity of studies in Pacific archipelagos near Asia and Australia, and in the Indian Ocean. Data on island frugivory and seed dispersal are diverse but highly uneven in geographic and conceptual coverage. Despite their limited biodiversity, islands are essential reservoirs of endemic plants and animals and their interactions. Due to the simplicity of insular ecosystems, we can assess the importance of seed dispersal theory and mechanisms at species and community levels. These include the ecological and biogeographical meaning and prevalence of non-standard mechanisms of seed dispersal on islands; the seed dispersal effectiveness and the relative roles of different frugivore guilds (birds and reptiles being the most important); and patterns of community organization and their drivers as revealed by interaction networks. Island systems are characterized by the extinction of many natives and endemics, and high rates of species introductions. Therefore, understanding how these losses and additions alter seed dispersal processes has been a prevailing goal of island studies and an essential foundation for the effective restoration and conservation of islands.

Corrigendum: Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2024)

Insects as radar targets: size, form, density and permittivity - V. Alistair Drake; Djordje Mirkovic; Martin J. Steinbauer (International Journal of Remote Sensing, 2024)

Local socioeconomic factors predict urban forest structure and composition across neighborhoods in Syracuse, NY (USA) - Jordan Jessamy; John E. Drake; David J. Nowak; John C. Stella (Landscape and Urban Planning, 2024)

Carbonaceous matter in ∼ 3.5 Ga black bedded barite from the Dresser Formation (Pilbara Craton, Western Australia) – Insights into organic cycling on the juvenile Earth - L. Weimann; M. Reinhardt; J.-P. Duda; H. Mißbach-Karmrodt; H. Drake; J. Schönig; J. Holburg; L.B. Andreas; J. Reitner; M.J. Whitehouse; V. Thiel (Precambrian Research, 2024)

Intrinsic and Extrinsic Regulation of Water Clarity in a Large, Floodplain River Ecosystem - Alicia M. Carhart; Deanne C. Drake; James R. Fischer; Jeffrey N. Houser; Kathi J. Jankowski; John E. Kalas; Eric M. Lund (Ecosystems, 2024)

Aspects of the biological carbon cycle in a ca. 3.42-billion-year-old marine ecosystem - M. Reinhardt; V. Thiel; J.-P. Duda; A. Hofmann; D. Bajnai; W. Goetz; A. Pack; J. Reitner; M. Schanofski; J. Schönig; M.J. Whitehouse; H. Drake (Precambrian Research, 2024)

Propagating Uncertainty in Predicting Individuals and Means Illustrated with Foliar Chemistry and Forest Biomass - Ruth D. Yanai; John E. Drake; Hannah L. Buckley; Bradley S. Case; Paul J. Lilly; Richard C. Woollons; Javier G. P. Gamarra (Ecosystems, 2024)
Quantifying uncertainty is important to establishing the significance of comparisons, to making predictions with known confidence, and to identifying priorities for investment. However, uncertainty can be difficult to quantify correctly. While sampling error is commonly reported based on replicate measurements, the uncertainty in regression models used to estimate forest biomass from tree dimensions is commonly ignored and has sometimes been reported incorrectly, due either to lack of clarity in recommended procedures or to incentives to underestimate uncertainties. Even more rarely are the uncertainty in predicting individuals and the uncertainty in the mean both recognized for their contributions to overall uncertainty. In this paper, we demonstrate the effect of propagating these two sources of uncertainty using a simple example of calcium concentration of sugar maple foliage, which does not require regression, then the mass of foliage and calcium content of foliage, and finally an entire forest with multiple species and tissue types. The uncertainty due to predicting individuals is greater than the uncertainty in the mean for studies with few trees—up to 30 trees for foliar calcium concentration and 50 trees for foliar mass and calcium content in the data set we analyzed from the Hubbard Brook Experimental Forest. The most correct analysis will take both sources of uncertainty into account, but for practical purposes, country-level reports of uncertainty in carbon stocks can safely ignore the uncertainty in individuals, which becomes negligible with large enough numbers of trees. Ignoring the uncertainty in the mean will result in exaggerated confidence in estimates of forest biomass and carbon and nutrient contents.

DNA metabarcoding reveals diet composition of invasive rats and mice in Hawaiian forests - Sara M. E. Gabrielson; Rebecca L. Mau; Erika Dittmar; J. Patrick Kelley; Corey E. Tarwater; Donald R. Drake; Jinelle H. Sperry; Jeffrey T. Foster (Biological Invasions, 2024)

Status of ash forests and regeneration a decade after first detection of emerald ash borer infestation in New York state - T.D. Morris; J.R. Gould; J. Drake; M.K. Fierke (Forest Ecology and Management, 2023)

Turbulent diapycnal fluxes as a pilot Essential Ocean Variable - Arnaud Le Boyer; Nicole Couto; Matthew H. Alford; Henri F. Drake; Cynthia E. Bluteau; Kenneth G. Hughes; Alberto C. Naveira Garabato; Aurélie J. Moulin; Thomas Peacock; Elizabeth C. Fine; Ali Mashayek; Laura Cimoli; et al. (Frontiers in Marine Science, 2023)
We contend that ocean turbulent fluxes should be included in the list of Essential Ocean Variables (EOVs) created by the Global Ocean Observing System. This list aims to identify variables that are essential to observe to inform policy and maintain a healthy and resilient ocean. Diapycnal turbulent fluxes quantify the rates of exchange of tracers (such as temperature, salinity, density or nutrients, all of which are already EOVs) across a density layer. Measuring them is necessary to close the tracer concentration budgets of these quantities. Measuring turbulent fluxes of buoyancy ( J b ), heat ( J q ), salinity ( J S ) or any other tracer requires either synchronous microscale (a few centimeters) measurements of both the vector velocity and the scalar (e.g., temperature) to produce time series of the highly correlated perturbations of the two variables, or microscale measurements of turbulent dissipation rates of kinetic energy ( ϵ ) and of thermal/salinity/tracer variance ( χ ), from which fluxes can be derived. Unlike isopycnal turbulent fluxes, which are dominated by the mesoscale (tens of kilometers), microscale diapycnal fluxes cannot be derived as the product of existing EOVs, but rather require observations at the appropriate scales. The instrumentation, standardization of measurement practices, and data coordination of turbulence observations have advanced greatly in the past decade and are becoming increasingly robust. With more routine measurements, we can begin to unravel the relationships between physical mixing processes and ecosystem health. In addition to laying out the scientific relevance of the turbulent diapycnal fluxes, this review also compiles the current developments steering the community toward such routine measurements, strengthening the case for registering the turbulent diapycnal fluxes as an pilot Essential Ocean Variable.

A decision-support framework for the restoration of Cystoseira sensu lato forests - Christopher J. Smith; Jana Verdura; Nadia Papadopoulou; Simonetta Fraschetti; Emma Cebrian; Erika Fabbrizzi; Margalida Monserrat; Matilde Drake; Silvia Bianchelli; Roberto Danovaro; Dania Abdul Malak; Enric Ballesteros; et al. (Frontiers in Marine Science, 2023)
Macroalgal forests characterised by species of the genus Cystoseira sensu lato form important shallow coastal rocky habitats in the Mediterranean Sea. These forests support a high biodiversity and provide important ecosystem services and societal benefits. Currently these habitats are often in a poor condition in many areas, due to loss and degradation from both anthropogenic and climate stressors. Restoration has recently moved to the forefront of the United Nations and European Union agendas to reverse this trend, particularly in the last decade with the implementation of various international policies. However, this has been in the form of generic targets (e.g., restoration of 30% of degraded habitats by 2030) and has not been linked to specifically what habitat or species to restore, where and how. Initial targets have been missed, new targets are expected through the proposed EU Nature Restoration Law, but overall guidance is still lacking. There are few specific guides to marine habitat restoration limited to mostly seagrass, corals and shellfish. As a priority action for the recovery of coastal marine ecosystems a decision-support framework has been developed for the restoration of Mediterranean macroalgal forests, comprising a stepwise decision tree with additional descriptions of key elements to be considered for a restoration action. The decision tree includes steps concerning current and historical forest presence, site local condition assessment and choice of actions. Key considerations include restoration implementation (competence, society and support, finance and governance), success evaluation (at the target species and the ecosystem level) and long-term management. The framework builds on existing work on Cystoseira s.l. restoration, the work carried out in the EU AFRIMED project, but also on principles and guidelines in place for both generic and specific marine habitats. The work reported here has involved the expertise of scientists and information from stakeholders. Gaps were identified and recommendations were made, dealing with stressors, coordinating and networking stakeholders, integrating top down policy and bottom up initiatives, funding of restoration actions, establishing synergies between restoration, conservation and marine spatial planning and finally communication and publicity.

Adapting a Research and Community Capacity-Building Program to Address Rural Cancer Burden and Facilitate Partnership Development Between Rural Community Stakeholders and an Urban Comprehensive Cancer Center - Marquita W. Lewis-Thames; Nora Leahy; Aaron J. Kruse-Diehr; Nicole Ackermann; Julia Maki; Kia L. Davis; Bettina F. Drake (Journal of Cancer Education, 2023)

Variation in plasma protein levels in House Finches (Haemorhous mexicanus): effects of season, disease state, and urbanization - Dean J. Drake; Kevin J. McGraw (Journal of Ornithology, 2023)

Food insecurity and disasters: predicting disparities in total and first-time food pantry visits during the COVID-19 pandemic - Alexandria J. Drake; Lora A. Phillips; Brajesh Karna; Shakthi Bharathi Murugesan; Lily K. Villa; Nathan A. Smith (Food Security, 2023)
In the U.S. state of Arizona, nearly one-third of households experienced food insecurity during the COVID-19 pandemic, an increase from one-fourth of households before the pandemic. Previous research on food insecurity in the wake of natural and human-instigated disasters demonstrates that groups vulnerable to food insecurity before a disaster are more susceptible to food insecurity during and after that disaster; however, less is known about whether this relationship also holds true during health-related disasters, such as the COVID-19 pandemic. We explore how the COVID-19 pandemic influenced urban food insecurity patterns by analyzing the socio-demographic characteristics of food pantry clients in Maricopa County, Arizona. Using data from Phoenix Rescue Mission (PRM), a local non-profit food service provider, two binomial logistic regression models compare the socio-demographic composition of total and first-time food pantry users before and during the pandemic. In addition to an overall increase in food pantry usage during the pandemic, we find that, while certain socio-demographic groups historically vulnerable to food insecurity experienced the predicted uptick in insecurity during the pandemic, other socio-demographic disparities were attenuated. These somewhat disparate findings illustrate the complex relationship between disasters and food insecurity in an urban context, offering several avenues for future research.

Disasters collide at the intersection of extreme weather and infectious diseases - John M. Drake; Éric Marty; Kamal J. K. Gandhi; Meredith Welch‐Devine; Brian Bledsoe; Marshall Shepherd; Lynne Seymour; Christine C. Fortuin; Cristian Montes (Ecology Letters, 2023)
Natural disasters interact to affect the resilience and prosperity of communities and disproportionately affect low income families and communities of colour. However, due to lack of a common theoretical framework, these are rarely quantified. Observing severe weather events (e.g. hurricanes and tornadoes) and epidemics (e.g. COVID‐19) unfolding in southeastern US communities led us to conjecture that interactions among catastrophic disturbances might be much more considerable than previously recognized. For instance, hurricane evacuations increase human aggregation, a factor that affects the transmission of acute infections like SARS‐CoV‐2. Similarly, weather damage to health infrastructure can reduce a community's ability to provide services to people who are ill. As globalization and human population and movement continue to increase and weather events are becoming more intense, such complex interactions are expected to magnify and significantly impact environmental and human health.

Early diagenetic processes in an iron-dominated marine depositional system - Maria C. Figueroa; Sebastiaan J. van de Velde; Daniel D. Gregory; Sydnie Lemieux; Jeana Drake; Tina Treude; Nathaniel Kemnitz; William Berelson; Konstantin Choumiline; Steven Bates; Ravi Kukkadapu; Marilyn Fogel; et al. (Geochimica et Cosmochimica Acta, 2023)

Hydrogeochemical and isotopic signatures elucidate deep subsurface hypersaline brine formation through radiolysis driven water-rock interaction - D.M. Nisson; T.L. Kieft; H. Drake; O. Warr; B. Sherwood Lollar; H. Ogasawara; S.M. Perl; B.M. Friefeld; J. Castillo; M.J. Whitehouse; E. Kooijman; T.C. Onstott (Geochimica et Cosmochimica Acta, 2023)

Introduced galliforms as seed predators and dispersers in Hawaiian forests - Samuel B. Case; Katherine Postelli; Donald R. Drake; Jeferson Vizentin-Bugoni; Jeffrey T. Foster; Jinelle H. Sperry; J. Patrick Kelley; Corey E. Tarwater (Biological Invasions, 2022)

Integrated Quadrant Analysis: A New Method for Analyzing Turbulent Coherent Structures - Mary Rose Mangan; Holly J. Oldroyd; Kyaw Tha Paw U; Jenae’ M. Clay; Stephen A. Drake; Jason Kelley; Kosana Suvočarev (Boundary-Layer Meteorology, 2022)
Integrated quadrant analysis is a novel technique to identify and to characterize the trajectory and strength of turbulent coherent structures in the atmospheric surface layer. By integrating the three-dimensional velocity field characterized by traditional quadrant analysis with respect to time, the trajectory history of individual coherent structures can be preserved with Eulerian turbulence measurements. We develop a method to identify the ejection phase of coherent structures based on turbulence kinetic energy (TKE). Identifying coherent structures within a time series using TKE performs better than identifying them with the streamwise and vertical velocity components because some coherent structures are dominated by the cross-stream velocity component as they pass the sensor. By combining this identification method with the integrated quadrant analysis, one can animate or plot the trajectory of individual coherent structures from high-frequency velocity measurements. This procedure links a coherent ejection with the subsequent sweep and quiescent period in time to visualize and quantify the strength and the duration of a coherent structure. We develop and verify the method of integrated quadrant analysis with data from two field studies: the Eclipse Boundary Layer Experiment (EBLE) in Corvallis, Oregon in August 2017 (grass field) and the Vertical Cherry Array Experiment (VACE) in Linden, California in November 2019 (cherry orchard). The combined TKE identification method and integrated quadrant analysis are promising additions to conditional sampling techniques and coherent structure characterization because the identify coherent structures and couple the sweep and ejection components in space. In an orchard (VACE), integrated quadrant analysis verifies each coherent structure is dominated by a sweep. Conversely, above the roughness sublayer (EBLE), each coherent structure is dominated by an ejection.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Mechanisms underlying lack of functional compensation by insect grazers after tadpole declines in a Neotropical stream - Thomas R. Barnum; John Timothy Wootton; Rebecca J. Bixby; John M. Drake; David Murray‐Stoker; Checo Colón‐Gaud; Amanda T. Rugenski; Therese C. Frauendorf; Scott Connelly; Susan S. Kilham; Matt R. Whiles; Karen R. Lips; et al. (Limnology and Oceanography, 2022)
Resilience of ecosystems to the sudden decline of large‐bodied species is dependent on characteristics of surviving guild members. However, that response may also be mediated by local habitat conditions. Here, we examine the mechanisms behind the observed lack of functional compensation in the algal‐grazing guild by insect grazers following the decline of tadpole grazers in a forested Panamanian stream. We examined: (1) shifts to the individual size distribution of insect grazers between pre‐ and post‐tadpole declines in pool and riffle habitats; (2) tadpole and insect preferences for small‐, medium‐, and large‐sized diatoms; and (3) a causal explanation for why insects did not functionally compensate for tadpole declines. The size distribution of insect grazers following tadpole declines differed between habitats, becoming uniform in pools and more right skewed toward a smaller size class in riffles. In both habitats, tadpoles selectively consumed medium‐sized diatoms but avoided the largest‐sized diatoms. In contrast, grazing insects selectively consumed small‐sized diatoms, but switched to medium‐sized diatoms after tadpole declines. Tadpole declines led to the loss of the strongest interactions between consumers and diatoms. Smaller‐bodied grazing insects could not duplicate these interactions, even with a shift in resource use, providing an explanation for the lack of functional compensation. Furthermore, tadpole declines led to different community structures in each habitat indicating that local habitat conditions mediated the response of surviving guild members. This suggests that the sudden decline of a large‐bodied species does not lead to a singular outcome for the surviving community.

Risks of giant hogweed (Heracleum mantegazzianum) range increase in North America - K. Cuddington; S. Sobek-Swant; J. Drake; W. Lee; M. Brook (Biological Invasions, 2022)

Understanding Constraints on Submersed Vegetation Distribution in a Large, Floodplain River: the Role of Water Level Fluctuations, Water Clarity and River Geomorphology - Alicia M. Carhart; John E. Kalas; James T. Rogala; Jason J. Rohweder; Deanne C. Drake; Jeffrey N. Houser (Wetlands, 2021)

Friend or foe? The role of biotic agents in drought-induced plant mortality - Robert J. Griffin-Nolan; Neha Mohanbabu; Sarah Araldi-Brondolo; Alexander R. Ebert; Julie LeVonne; Joanna I. Lumbsden-Pinto; Hannah Roden; Jordan R. Stark; Jordon Tourville; Katie M. Becklin; John E. Drake; Douglas A. Frank; et al. (Plant Ecology, 2021)

Direct effects influence larval salamander size and density more than indirect effects - Thomas L. Anderson; Brittany H. Ousterhout; Freya E. Rowland; Dana L. Drake; Jacob J. Burkhart; William E. Peterman (Oecologia, 2021)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Characterizing species co‐occurrence patterns of imperfectly detected stream fishes to inform species reintroduction efforts - Karl A. Lamothe; Alan J. Dextrase; D. Andrew R. Drake (Conservation Biology, 2019)
Species reintroduction efforts can improve the recovery of imperiled species, but successful implementation of this conservation strategy requires a thorough understanding of the abiotic and biotic factors influencing species viability. Species interactions are especially understudied, in particular by omitting the effect of imperfect detection on negative, neutral, or positive associations within a community. Using repeat surveys from 5 southern Ontario, Canada, Great Lakes tributaries, we quantified species co‐occurrence patterns with the eastern sand darter (ESD) ( Ammocrypta pellucida ), listed as federally threatened, and characterized how imperfect detection during sampling can influence inference regarding these relationships. We used a probabilistic framework that included 3 approaches of increasing complexity: probabilistic co‐occurrence analysis ignoring imperfect detection; single‐species occupancy models with subsequent co‐occurrence analysis; and 2‐species occupancy models. We then used our occupancy models to predict suitable sites for potential future reintroduction efforts while considering the influence of negative species interactions. Based on the observed data, ESD showed several positive associations with co‐occurring species; however, species associations differed when imperfect detection was considered. Specifically, a negative association between ESD and rosyface shiner ( Notropis rubellus ) was observed only after accounting for imperfect detection in the Grand River. Alternatively, positive associations in the Grand River between ESD and northern hogsucker ( Hypentelium nigricans ) and silver shiner ( Notropis photogenis ) were observed regardless of whether imperfect detection was accounted for. Our models predicted several potential reintroduction sites for ESD in formerly occupied watersheds with high levels of certainty. Overall, our results demonstrate the importance of investigating imperfect detection and species co‐occurrence when planning reintroduction efforts.

Contrasting latitudinal gradients of body size in helminth parasites and their hosts - Tad Dallas; Alyssa‐Lois M. Gehman; A. Alonso Aguirre; Sarah A. Budischak; John M. Drake; Maxwell J. Farrell; Ria Ghai; Shan Huang; Ignacio Morales‐Castilla (Global Ecology and Biogeography, 2019)
Aim We examined body size scaling relationships for two developmental life stages of parasitic helminths (egg and adult) separately in relationship to latitude (i.e. Bergmann's rule), temperature and temperature seasonality. Given that helminth eggs experience environmental conditions more directly, whereas adults live inside infected host individuals, we predict stronger environmentally driven gradients of body size for eggs than for adults. Location Global. Time period Present day. Major taxa studied Parasitic helminths. Methods We compiled egg size and adult body size data (both minimum and maximum) for 265 parasitic helminth species from the literature, along with species latitudinal distribution information using an extensive global helminth occurrence database. We then examined how the average helminth egg and adult body size of all helminth species present (minimum and maximum separately) scaled with latitude, temperature and temperature variability, using generalized linear models. Results Both the egg size and the adult body size of helminths tended to decrease towards higher latitudes, although we found the opposite body size scaling pattern for their host species. Helminth sizes were also positively correlated with temperature and negatively, but more weakly, with temperature seasonality. Main conclusions Instead of following the body size patterns of their hosts, helminth parasites are more similar to other ectotherms in that they follow the converse Bergmann's rule. This pattern did not differ between helminth developmental stages, suggesting that mean annual temperature and seasonality are unlikely to be related mechanistically to body size variation in this case.

Range size and growth temperature influence Eucalyptus species responses to an experimental heatwave - Michael J. Aspinwall; Sebastian Pfautsch; Mark G. Tjoelker; Angelica Vårhammar; Malcolm Possell; John E. Drake; Peter B. Reich; David T. Tissue; Owen K. Atkin; Paul D. Rymer; Siobhan Dennison; Steven C. Van Sluyter (Global Change Biology, 2019)
Understanding forest tree responses to climate warming and heatwaves is important for predicting changes in tree species diversity, forest C uptake, and vegetation–climate interactions. Yet, tree species differences in heatwave tolerance and their plasticity to growth temperature remain poorly understood. In this study, populations of four Eucalyptus species, two with large range sizes and two with comparatively small range sizes, were grown under two temperature treatments (cool and warm) before being exposed to an equivalent experimental heatwave. We tested whether the species with large and small range sizes differed in heatwave tolerance, and whether trees grown under warmer temperatures were more tolerant of heatwave conditions than trees grown under cooler temperatures. Visible heatwave damage was more common and severe in the species with small rather than large range sizes. In general, species that showed less tissue damage maintained higher stomatal conductance, lower leaf temperatures, larger increases in isoprene emissions, and less photosynthetic inhibition than species that showed more damage. Species exhibiting more severe visible damage had larger increases in heat shock proteins (HSPs) and respiratory thermotolerance ( T max ). Thus, across species, increases in HSPs and T max were positively correlated, but inversely related to increases in isoprene emissions. Integration of leaf gas‐exchange, isoprene emissions, proteomics, and respiratory thermotolerance measurements provided new insight into mechanisms underlying variability in tree species heatwave tolerance. Importantly, warm‐grown seedlings were, surprisingly, more susceptible to heatwave damage than cool‐grown seedlings, which could be associated with reduced enzyme concentrations in leaves. We conclude that species with restricted range sizes, along with trees growing under climate warming, may be more vulnerable to heatwaves of the future.

European Pinnotheridae (Crustacea, Decapoda, Brachyura): species, distribution, host use and DNA barcodes - M. Perez-Miguel; P. Drake; J. E. García Raso; L. Mamán Menéndez; J. I. Navas; J. A. Cuesta (Marine Biodiversity, 2019)

Agricultural conservation practices in Iowa watersheds: comparing actual implementation with practice potential - Trevor J. Rundhaug; Greg R. Geimer; Chad W. Drake; Antonio Arenas Amado; A. Allen Bradley; Calvin F. Wolter; Larry J. Weber (Environmental Monitoring and Assessment, 2018)

Design, Modelling and Teleoperation of a 2 mm Diameter Compliant Instrument for the da Vinci Platform - P. Francis; K. W. Eastwood; V. Bodani; T. Looi; J. M. Drake (Annals of Biomedical Engineering, 2018)

Photosynthetic capacity and leaf nitrogen decline along a controlled climate gradient in provenances of two widely distributed Eucalyptus species - Kristine Y. Crous; John E. Drake; Michael J. Aspinwall; Robert E. Sharwood; Mark G. Tjoelker; Oula Ghannoum (Global Change Biology, 2018)
Climate is an important factor limiting tree distributions and adaptation to different thermal environments may influence how tree populations respond to climate warming. Given the current rate of warming, it has been hypothesized that tree populations in warmer, more thermally stable climates may have limited capacity to respond physiologically to warming compared to populations from cooler, more seasonal climates. We determined in a controlled environment how several provenances of widely distributed Eucalyptus tereticornis and E. grandis adjusted their photosynthetic capacity to +3.5°C warming along their native distribution range (~16–38°S) and whether climate of seed origin of the provenances influenced their response to different growth temperatures. We also tested how temperature optima ( T opt ) of photosynthesis and J max responded to higher growth temperatures. Our results showed increased photosynthesis rates at a standardized temperature with warming in temperate provenances, while rates in tropical provenances were reduced by about 40% compared to their temperate counterparts. Temperature optima of photosynthesis increased as provenances were exposed to warmer growth temperatures. Both species had ~30% reduced photosynthetic capacity in tropical and subtropical provenances related to reduced leaf nitrogen and leaf Rubisco content compared to temperate provenances. Tropical provenances operated closer to their thermal optimum and came within 3% of the T opt of J max during the daily temperature maxima. Hence, further warming may negatively affect C uptake and tree growth in warmer climates, whereas eucalypts in cooler climates may benefit from moderate warming.

Trees tolerate an extreme heatwave via sustained transpirational cooling and increased leaf thermal tolerance - John E. Drake; Mark G. Tjoelker; Angelica Vårhammar; Belinda E. Medlyn; Peter B. Reich; Andrea Leigh; Sebastian Pfautsch; Chris J. Blackman; Rosana López; Michael J. Aspinwall; Kristine Y. Crous; Remko A. Duursma; et al. (Global Change Biology, 2018)
Heatwaves are likely to increase in frequency and intensity with climate change, which may impair tree function and forest C uptake. However, we have little information regarding the impact of extreme heatwaves on the physiological performance of large trees in the field. Here, we grew Eucalyptus parramattensis trees for 1 year with experimental warming (+3°C) in a field setting, until they were greater than 6 m tall. We withheld irrigation for 1 month to dry the surface soils and then implemented an extreme heatwave treatment of 4 consecutive days with air temperatures exceeding 43°C, while monitoring whole‐canopy exchange of CO 2 and H 2 O, leaf temperatures, leaf thermal tolerance, and leaf and branch hydraulic status. The heatwave reduced midday canopy photosynthesis to near zero but transpiration persisted, maintaining canopy cooling. A standard photosynthetic model was unable to capture the observed decoupling between photosynthesis and transpiration at high temperatures, suggesting that climate models may underestimate a moderating feedback of vegetation on heatwave intensity. The heatwave also triggered a rapid increase in leaf thermal tolerance, such that leaf temperatures observed during the heatwave were maintained within the thermal limits of leaf function. All responses were equivalent for trees with a prior history of ambient and warmed (+3°C) temperatures, indicating that climate warming conferred no added tolerance of heatwaves expected in the future. This coordinated physiological response utilizing latent cooling and adjustment of thermal thresholds has implications for tree tolerance of future climate extremes as well as model predictions of future heatwave intensity at landscape and global scales.

Mapping and Modeling Ecological Conditions of Longleaf Pine Habitats in the Apalachicola National Forest - Matthew D Trager; Jason B Drake; Amy M Jenkins; Carl J Petrick (Journal of Forestry, 2018)

Ultrasonic motor-induced geometric distortions in magnetic resonance images - P. Shokrollahi; J. M. Drake; A. A. Goldenberg (Medical & Biological Engineering & Computing, 2018)

Ventral-aspect radar cross sections and polarization patterns of insects at X band and their relation to size and form - V. A. Drake; J. W. Chapman; K. S. Lim; D. R. Reynolds; J. R. Riley; A. D. Smith (International Journal of Remote Sensing, 2017)

Allometry data and equations for coastal marsh plants - Meng Lu; Joshua S. Caplan; Jonathan D. Bakker; J. Adam Langley; Thomas J. Mozdzer; Bert G. Drake; J. Patrick Megonigal (Ecology, 2016)
Coastal marshes are highly valued for ecosystem services such as protecting inland habitats from storms, sequestering carbon, removing nutrients and other pollutants from surface water, and providing habitat for fish, shellfish, and birds. Because plants largely determine the structure and function of coastal marshes, quantifying plant biomass is essential for evaluating these ecosystem services, understanding the biogeochemical processes that regulate ecosystem function, and forecasting tidal wetland responses to accelerated sea level rise. Allometry is a convenient and efficient technique for nondestructive estimation of plant biomass, and it is commonly used in studies of carbon and nitrogen cycles, energy flows, and marsh surface elevation change. We present plant allometry data and models developed for three long‐term experiments at the Smithsonian Global Change Research Wetland, a brackish marsh in the Rhode River subestuary of the Chesapeake Bay. The dataset contains 9,771 measurements of stem height, dry mass, and (in 9638 cases) stem width across 11 plant species. The vast majority of observations are for Schoenoplectus americanus (8430) and Phragmites australis (311), with fewer observations for other common species: Amaranthus cannabinus , Atriplex patula , Iva frutescens , Kosteletzkya virginica , Polygonum hydropiper , Solidago sempervirens , Spartina alterniflora , Spartina cynosuroides , and Typha angustifolia . Allometric relationships take the form of linear regressions of biomass (transformed using the Box‐Cox procedure) on either stem height and width, or on stem height alone. Allometric relationships for Schoenoplectus americanus were not meaningfully altered by elevated CO 2 , N enrichment, the community context, interannual variation in climate, or year, showing that a single equation can be used across a broad range of conditions for this species. Archived files include: (1) raw data used to derive allometric equations for each species, (2) reports and evaluations of the allometric equations we derived from the data, and (3) R code with which our derivations can be replicated. Methodological details of our experiments, data collection efforts, and statistical modeling are described in the metadata. The allometric equations can be used for biomass estimation in empirical and modeling studies of North American coastal wetlands, and the data can be used in ecological studies of terrestrial plant allometry.

When can the cause of a population decline be determined? - Trevor J. Hefley; Mevin B. Hooten; John M. Drake; Robin E. Russell; Daniel P. Walsh (Ecology Letters, 2016)
Inferring the factors responsible for declines in abundance is a prerequisite to preventing the extinction of wild populations. Many of the policies and programmes intended to prevent extinctions operate on the assumption that the factors driving the decline of a population can be determined. Exogenous factors that cause declines in abundance can be statistically confounded with endogenous factors such as density dependence. To demonstrate the potential for confounding, we used an experiment where replicated populations were driven to extinction by gradually manipulating habitat quality. In many of the replicated populations, habitat quality and density dependence were confounded, which obscured causal inference. Our results show that confounding is likely to occur when the exogenous factors that are driving the decline change gradually over time. Our study has direct implications for wild populations, because many factors that could drive a population to extinction change gradually through time.

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Using models to guide field experiments: a priori predictions for the CO 2 response of a nutrient‐ and water‐limited native Eucalypt woodland - Belinda E. Medlyn; Martin G. De Kauwe; Sönke Zaehle; Anthony P. Walker; Remko A. Duursma; Kristina Luus; Mikhail Mishurov; Bernard Pak; Benjamin Smith; Ying‐Ping Wang; Xiaojuan Yang; Kristine Y. Crous; et al. (Global Change Biology, 2016)
The response of terrestrial ecosystems to rising atmospheric CO 2 concentration (C a ), particularly under nutrient‐limited conditions, is a major uncertainty in Earth System models. The Eucalyptus Free‐Air CO 2 Enrichment (Euc FACE ) experiment, recently established in a nutrient‐ and water‐limited woodland presents a unique opportunity to address this uncertainty, but can best do so if key model uncertainties have been identified in advance. We applied seven vegetation models, which have previously been comprehensively assessed against earlier forest FACE experiments, to simulate a priori possible outcomes from Euc FACE . Our goals were to provide quantitative projections against which to evaluate data as they are collected, and to identify key measurements that should be made in the experiment to allow discrimination among alternative model assumptions in a postexperiment model intercomparison. Simulated responses of annual net primary productivity ( NPP ) to elevated C a ranged from 0.5 to 25% across models. The simulated reduction of NPP during a low‐rainfall year also varied widely, from 24 to 70%. Key processes where assumptions caused disagreement among models included nutrient limitations to growth; feedbacks to nutrient uptake; autotrophic respiration; and the impact of low soil moisture availability on plant processes. Knowledge of the causes of variation among models is now guiding data collection in the experiment, with the expectation that the experimental data can optimally inform future model improvements.

Competition‐mediated feedbacks in experimental multispecies epizootics - Tad Dallas; Richard J. Hall; John M. Drake (Ecology, 2016)
Competition structures ecological communities and alters host–pathogen interactions. In environmentally transmitted pathogens, an infection‐resistant competitor may influence infection dynamics in a susceptible species through the negative impacts of competition (e.g., by reducing host density or causing nutritional stress that increases susceptibility to infection) and/or the positive impacts of reducing transmission efficiency (e.g., by removing environmental pathogen stages). Thus, a non‐susceptible competitor may enhance, reduce, or have no net effect on susceptible host density and infection prevalence. Here, we couple an epidemiological model with experimental epidemics to test how resource competition with a non‐susceptible competitor ( Daphnia pulicaria ) influences fungal microparasite ( Metschnikowia bicuspidata ) infection dynamics in a susceptible host species ( D. dentifera ). Our model and experiments suggest that competitor density can mediate the direction and magnitude of the effect of competition on infection dynamics, with a peak in infection prevalence occurring at intermediate competitor densities. At low densities, the non‐susceptible competitor D. pulicaria may reduce infection prevalence in the susceptible host by removing fungal spores from the environment through feeding. However, when competitor density is increased and resources become limiting, D. pulicaria negatively impacts the susceptible host by increasing susceptible host feeding rates, and therefore fungal spore intake, and further by reducing susceptible host population size as it is driven toward competitive exclusion. In conclusion, these results show that a tradeoff between the competitor as a consumer of pathogen, which serves to reduce epidemic size, and as a modifier of susceptible host foraging ecology, which influences infection rates, may alternately enhance or dampen the magnitude of local epidemics.

Larval development of the pea crab Afropinnotheres monodi Manning, 1993 (Decapoda, Pinnotheridae) using plankton-collected and laboratory-reared specimens: effects of temperature - Elena Marco-Herrero; Pilar Drake; J. Ignacio González-Gordillo; Jose A. Cuesta (Marine Biology Research, 2016)

Efficacy of Multivitamin/mineral Supplementation to Reduce Chronic Disease Risk: A Critical Review of the Evidence from Observational Studies and Randomized Controlled Trials - Giana Angelo; Victoria J. Drake; Balz Frei (Critical Reviews in Food Science and Nutrition, 2015)

Automated analysis of temperature variance to determine inundation state of wetlands - Thomas L. Anderson; Jennifer L. Heemeyer; William E. Peterman; Michael J. Everson; Brittany H. Ousterhout; Dana L. Drake; Raymond D. Semlitsch (Wetlands Ecology and Management, 2015)

Erratum to: Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

Calibration and cross-validation of MCCB and CogState in schizophrenia - Jane Lees; Eve Applegate; Richard Emsley; Shôn Lewis; Panayiota Michalopoulou; Tracey Collier; Cristina Lopez-Lopez; Shitij Kapur; Gahan J. Pandina; Richard J. Drake (Psychopharmacology, 2015)

Clinical Immunogenicity of rHuPH20, a Hyaluronidase Enabling Subcutaneous Drug Administration - Sanna Rosengren; Samuel S. Dychter; Marie A. Printz; Lei Huang; Richard I. Schiff; Hans-Peter Schwarz; John K. McVey; Fred H. Drake; Dan C. Maneval; Don A. Kennard; Gregory I. Frost; Barry J. Sugarman; et al. (The AAPS Journal, 2015)

The capacity to cope with climate warming declines from temperate to tropical latitudes in two widely distributed Eucalyptus species - John E. Drake; Michael J. Aspinwall; Sebastian Pfautsch; Paul D. Rymer; Peter B. Reich; Renee A. Smith; Kristine Y. Crous; David T. Tissue; Oula Ghannoum; Mark G. Tjoelker (Global Change Biology, 2015)
As rapid climate warming creates a mismatch between forest trees and their home environment, the ability of trees to cope with warming depends on their capacity to physiologically adjust to higher temperatures. In widespread species, individual trees in cooler home climates are hypothesized to more successfully acclimate to warming than their counterparts in warmer climates that may approach thermal limits. We tested this prediction with a climate‐shift experiment in widely distributed Eucalyptus tereticornis and E. grandis using provenances originating along a ~2500 km latitudinal transect (15.5–38.0°S) in eastern Australia. We grew 21 provenances in conditions approximating summer temperatures at seed origin and warmed temperatures (+3.5 °C) using a series of climate‐controlled glasshouse bays. The effects of +3.5 °C warming strongly depended on home climate. Cool‐origin provenances responded to warming through an increase in photosynthetic capacity and total leaf area, leading to enhanced growth of 20–60%. Warm‐origin provenances, however, responded to warming through a reduction in photosynthetic capacity and total leaf area, leading to reduced growth of approximately 10%. These results suggest that there is predictable intraspecific variation in the capacity of trees to respond to warming; cool‐origin taxa are likely to benefit from warming, while warm‐origin taxa may be negatively affected.

Variation in propagule and colonization pressures following rapid human‐mediated transport: Implications for a universal assemblage‐based management model - Elizabeta Briski; D. Andrew R. Drake; Farrah T. Chan; Sarah A. Bailey; Hugh J. MacIsaac (Limnology and Oceanography, 2014)
Recent studies have recognized the importance of propagule pressure (number of individuals) and colonization pressure (number of species) for explaining establishment success of nonindigenous species. However, the International Ballast Water Management Convention, when ratified, will require ships to satisfy a numeric discharge standard that focuses only on cumulative propagule pressure of all individuals released. Because of practical constraints, the standard does not differentiate between discharges of single vs. multiple species. The assemblage‐based approach, which uses rank‐abundance gradients to quantify and manage introduction risk, may compensate for this limitation (e.g., even gradient [relatively consistent propagule pressures among n transported species] or uneven gradient [uneven propagule pressures among n transported species]). Here we explore species abundance distributions of zooplankton during transportation in ballast water to assess variability in the structure of assemblages, with implications for the potential development of an assemblage‐based management model. Specifically, we explored species abundance distributions for voyages that lasted

New insights into the genetic structure of Araucaria araucana forests based on molecular and historic evidences - M. A. Martín; C. Mattioni; I. Lusini; J. R. Molina; M. Cherubini; F. Drake; M. A. Herrera; F. Villani; L. M. Martín (Tree Genetics & Genomes, 2014)

3D imaging provides a high-resolution, volumetric approach for analyzing biofouling - Matthew R. First; Steven A. Policastro; Matthew J. Strom; Scott C. Riley; Stephanie H. Robbins-Wamsley; Lisa A. Drake (Biofouling, 2014)

Scaffold-Free Tissue Engineering: Organization of the Tissue Cytoskeleton and Its Effects on Tissue Shape - Caitlin A. Czajka; Agnes Nagy Mehesz; Thomas C. Trusk; Michael J. Yost; Christopher J. Drake (Annals of Biomedical Engineering, 2014)

Early Airway Structural Changes in Cystic Fibrosis Pigs as a Determinant of Particle Distribution and Deposition - Maged Awadalla; Shinjiro Miyawaki; Mahmoud H. Abou Alaiwa; Ryan J. Adam; Drake C. Bouzek; Andrew S. Michalski; Matthew K. Fuld; Karen J. Reynolds; Eric A. Hoffman; Ching-Long Lin; David A. Stoltz (Annals of Biomedical Engineering, 2014)

Winter habitat use does not influence spring arrival dates or the reproductive success of Yellow Warblers breeding in the arctic - Anna Drake; Michaela Martin; David J. Green (Polar Biology, 2014)

Direct and indirect effects of elevated atmospheric CO 2 on net ecosystem production in a Chesapeake Bay tidal wetland - John E. Erickson; Gary Peresta; Kathryn J. Montovan; Bert G. Drake (Global Change Biology, 2013)
The rapid increase in atmospheric CO 2 concentrations ( C a ) has resulted in extensive research efforts to understand its impact on terrestrial ecosystems, especially carbon balance. Despite these efforts, there are relatively few data comparing net ecosystem exchange of CO 2 between the atmosphere and the biosphere ( NEE ), under both ambient and elevated C a . Here we report data on annual sums of CO 2 ( NEE net ) for 19 years on a Chesapeake Bay tidal wetland for S cirpus olneyi (C 3 photosynthetic pathway)‐ and Spartina patens (C 4 photosynthetic pathway)‐dominated high marsh communities exposed to ambient and elevated C a (ambient + 340 ppm). Our objectives were to (i) quantify effects of elevated C a on seasonally integrated CO 2 assimilation ( NEE net = NEE day + NEE night , kg C m −2 y −1 ) for the two communities; and (ii) quantify effects of altered canopy N content on ecosystem photosynthesis and respiration. Across all years, NEE net averaged 1.9 kg m −2 y −1 in ambient C a and 2.5 kg m −2 y −1 in elevated C a , for the C 3 ‐dominated community. Similarly, elevated C a significantly ( P 4 ‐dominated community, as NEE net averaged 1.5 kg m −2 y −1 in ambient C a and 1.7 kg m −2 y −1 in elevated C a . This resulted in an average CO 2 stimulation of 32% and 13% of seasonally integrated NEE net for the C 3 ‐ and C 4 ‐dominated communities, respectively. Increased NEE day was correlated with increased efficiencies of light and nitrogen use for net carbon assimilation under elevated C a , while decreased NEE night was associated with lower canopy nitrogen content. These results suggest that rising C a may increase carbon assimilation in both C 3 ‐ and C 4 ‐dominated wetland communities. The challenge remains to identify the fate of the assimilated carbon.

Dispersal limitation, speciation, environmental filtering and niche differentiation influence forest tree communities in West Polynesia - Janet Franklin; Gunnar Keppel; Edward L. Webb; Joshua O. Seamon; Sergio J. Rey; David W. Steadman; Susan K. Wiser; Donald R. Drake (Journal of Biogeography, 2013)
Aim Regional patterns of forest composition in West Polynesia were analysed to determine the relative importance of dispersal limitation, speciation, environmental filtering and biotic interactions. Location West Polynesia (Fiji, Tonga, Samoa). Methods We applied clustering and indicator species analysis to presence/absence data for 397 tree taxa in 338 forest plots to detect groups of plots sharing similar species composition. Patterns of plot composition and co‐occurrence of congeneric species were compared between archipelagos for evidence of dispersal limitation, speciation, and environmental filtering versus competitive displacement or niche differentiation across the three archipelagos at the local (plot) and regional scales. Results Dispersal limitation was evident in the compositional segregation of inland rain forests across the three archipelagos, whereas compositional overlap was widespread for coastal forests, which are composed of species dispersed by water. Within genera, species numbers attenuated from Fiji to Tonga to Samoa, but speciation also contributed to compositional differences in all three island groups. Environmental filtering was suggested by the distinct composition of both secondary and mature inland rain forest versus coastal forest. At the local scale, however, clumping of congeners, which might suggest fine‐scale environmental filtering, was observed for only a minority of inland forest genera. Most genera showed either overdispersion, suggesting competitive displacement or niche differentiation, or patterns not significantly different from random. Main conclusions Well‐established biogeographical patterns of dispersal limitation and speciation contribute to West Polynesian tree diversity at the community scale. Environmental filtering and competitive displacement further structure forest communities; the evidence from this study suggests that environmental filtering is more important at a landscape scale, while competitive displacement may be more important at a local scale, although their relative importance varies considerably among taxa.

The propagation and dispersal of misinformation in ecology: Is there a relationship between citation accuracy and journal impact factor? - D. C. Drake; B. Maritz; S. M. Jacobs; C. J. Crous; A. Engelbrecht; A. Etale; M. J. Fourie; D. G. Furniss; S. L. Scott; S. Parusnath; D. R. Tye (Hydrobiologia, 2013)

Hybrid mouse diversity panel: a panel of inbred mouse strains suitable for analysis of complex genetic traits - Anatole Ghazalpour; Christoph D. Rau; Charles R. Farber; Brian J. Bennett; Luz D. Orozco; Atila van Nas; Calvin Pan; Hooman Allayee; Simon W. Beaven; Mete Civelek; Richard C. Davis; Thomas A. Drake; et al. (Mammalian Genome, 2012)

Comparison of techniques used to count single-celled viable phytoplankton - Mia K. Steinberg; Matthew R. First; Edward J. Lemieux; Lisa A. Drake; Bruce N. Nelson; David M. Kulis; Donald M. Anderson; Nicholas A. Welschmeyer; Penny R. Herring (Journal of Applied Phycology, 2012)

Enhanced Autologous Re-endothelialization of Decellularized and Extracellular Matrix Conditioned Allografts Implanted Into the Right Ventricular Outflow Tracts of Juvenile Sheep - Rachael W. Quinn; Stephen L. Hilbert; Gabriel L. Converse; Arthur A. Bert; Eric Buse; William B. Drake; Matt Armstrong; Sara J. Moriarty; Gary K. Lofland; Richard A. Hopkins (Cardiovascular Engineering and Technology, 2012)

Conservation status of eulachon in the California Current - Richard G Gustafson; Michael J Ford; Peter B Adams; Jonathan S Drake; Robert L Emmett; Kurt L Fresh; Mindy Rowse; Elizabeth A K Spangler; Robert E Spangler; David J Teel; Matthew T Wilson (Fish and Fisheries, 2012)
Eulachon ( Thaleichthys pacificus ), an anadromous smelt in the Northeast Pacific Ocean was examined for listing under the USA’s Endangered Species Act (ESA). A southern Distinct Population Segment (DPS) of eulachon – that occurs in the California Current and is composed of numerous subpopulations that spawn in rivers from northern California to northern British Columbia – was identified on the basis of ecological and environmental characteristics, and to a lesser extent, genetic and life history variation. Although the northern terrestrial boundary of this DPS remains uncertain, our consensus opinion was that this northern boundary occurs south of the Nass River and that the DPS was discrete from more northern eulachon, as well as significant to the biological species as a whole and thus is a ‘species’ under the ESA. Eulachon have been nearly absent in northern California for over two decades, have declined in the Fraser River by over 97% in the past 10 years, and are at historically low levels in other British Columbia rivers in the DPS, and nearly so in the Columbia River. Major threats to southern eulachon include climate change impacts on ocean and freshwater habitat, by‐catch in offshore shrimp trawl fisheries, changes in downstream flow timing and intensity owing to dams and water diversions, and predation. These threats, together with large declines in abundance, indicate that the southern DPS of eulachon is at moderate risk of extinction throughout all of its range. The southern DPS was listed as threatened under the ESA in May 2010 – the first marine forage fish to be afforded these statutory protections, which apply only to waters under U.S. jurisdiction.

The effect of periphyton stoichiometry and light on biological phosphorus immobilization and release in streams - W. M. Drake; J. Thad Scott; Michelle Evans-White; Brian Haggard; Andrew Sharpley; Chris W. Rogers; Erin M. Grantz (Limnology, 2012)

Nitrogen source and p CO 2 synergistically affect carbon allocation, growth and morphology of the coccolithophore E miliania huxleyi : potential implications of ocean acidification for the carbon cycle - Stephane C. Lefebvre; Ina Benner; Jonathon H. Stillman; Alexander E. Parker; Michelle K. Drake; Pascale E. Rossignol; Kristine M. Okimura; Tomoko Komada; Edward J. Carpenter (Global Change Biology, 2012)
Coccolithophores are unicellular phytoplankton that produce calcium carbonate coccoliths as an exoskeleton. E miliania huxleyi , the most abundant coccolithophore in the world's ocean, plays a major role in the global carbon cycle by regulating the exchange of CO 2 across the ocean‐atmosphere interface through photosynthesis and calcium carbonate precipitation. As CO 2 concentration is rising in the atmosphere, the ocean is acidifying and ammonium ( NH 4 + ) concentration of future ocean water is expected to rise. The latter is attributed to increasing anthropogenic nitrogen ( N ) deposition, increasing rates of cyanobacterial N 2 fixation due to warmer and more stratified oceans, and decreased rates of nitrification due to ocean acidification. Thus, future global climate change will cause oceanic phytoplankton to experience changes in multiple environmental parameters including CO 2 , pH , temperature and nitrogen source. This study reports on the combined effect of elevated p CO 2 and increased NH 4 + to nitrate ( NO 3 − ) ratio ( NH 4 + / NO 3 − ) on E . huxleyi, maintained in continuous cultures for more than 200 generations under two p CO 2 levels and two different N sources. Herein, we show that NH 4 + assimilation under N ‐replete conditions depresses calcification at both low and high p CO 2 , alters coccolith morphology, and increases primary production. We observed that N source and p CO 2 synergistically drive growth rates, cell size, and the ratio of inorganic to organic carbon. These responses to N source suggest that, compared to increasing CO 2 alone, a greater disruption of the organic carbon pump could be expected in response to the combined effect of increased NH 4 + / NO 3 − ratio and CO 2 level in the future acidified ocean. Additional experiments conducted under lower nutrient conditions are needed prior to extrapolating our findings to the global oceans. Nonetheless, our results emphasize the need to assess combined effects of multiple environmental parameters on phytoplankton biology to develop accurate predictions of phytoplankton responses to ocean acidification.

Determining the viability of marine protists using a combination of vital, fluorescent stains - Mia K. Steinberg; Edward J. Lemieux; Lisa A. Drake (Marine Biology, 2011)

Generation of transgenic plants expressing plasma membrane-bound antibodies to the environmental pollutant microcystin-LR - Tommaso Barbi; Pascal M. W. Drake; Matthew Drever; Craig J. van Dolleweerd; Andrew R. Porter; Julian K-C. Ma (Transgenic Research, 2011)

Critical patch size generated by Allee effect in gypsy moth, Lymantria dispar (L.) - E. Vercken; A. M. Kramer; P. C. Tobin; J. M. Drake (Ecology Letters, 2011)
Ecology Letters (2011) 14: 179–186 Abstract Allee effects are important dynamical mechanisms in small‐density populations in which per capita population growth rate increases with density. When positive density dependence is sufficiently severe (a ‘strong’ Allee effect), a critical density arises below which populations do not persist. For spatially distributed populations subject to dispersal, theory predicts that the occupied area also exhibits a critical threshold for population persistence, but this result has not been confirmed in nature. We tested this prediction in patterns of population persistence across the invasion front of the European gypsy moth ( Lymantria dispar ) in the United States in data collected between 1996 and 2008. Our analysis consistently provided evidence for effects of both population area and density on persistence, as predicted by the general theory, and confirmed here using a mechanistic model developed for the gypsy moth system. We believe this study to be the first empirical documentation of critical patch size induced by an Allee effect.

Effects of light and nutrients on seasonal phytoplankton succession in a temperate eutrophic coastal lagoon - Jeana L. Drake; Edward J. Carpenter; Mary Cousins; Kara L. Nelson; Alejandro Guido-Zarate; Keith Loftin (Hydrobiologia, 2010)

Intra-individual variation in serum C-reactive protein over 4 years: an implication for epidemiologic studies - Elizabeth A. Platz; Siobhan Sutcliffe; Angelo M. De Marzo; Charles G. Drake; Nader Rifai; Ann W. Hsing; Ashraful Hoque; Marian L. Neuhouser; Phyllis J. Goodman; Alan R. Kristal (Cancer Causes & Control, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Modification of a French pressure cell to improve microbial cell disruption - Paul R. Jaschke; Ian Drake; J. Thomas Beatty (Photosynthesis Research, 2009)

Salt marsh ecosystem biogeochemical responses to nutrient enrichment: a paired 15 N tracer study - D. C. Drake; Bruce J. Peterson; Kari A. Galván; Linda A. Deegan; Charles Hopkinson; J. Michael Johnson; K. Koop-Jakobsen; Lynsey E. Lemay; Christian Picard (Ecology, 2009)
We compared processing and fate of dissolved NO 3 − in two New England salt marsh ecosystems, one receiving natural flood tide concentrations of ∼1–4 μmol NO 3 − /L and the other receiving experimentally fertilized flood tides containing ∼70–100 μmol NO 3 − /L. We conducted simultaneous 15 NO 3 − (isotope) tracer additions from 23 to 28 July 2005 in the reference (8.4 ha) and fertilized (12.4 ha) systems to compare N dynamics and fate. Two full tidal cycles were intensively studied during the paired tracer additions. Resulting mass balances showed that essentially 100% (0.48–0.61 mol NO 3 ‐N·ha −1 ·h −1 ) of incoming NO 3 − was assimilated, dissimilated, sorbed, or sedimented (processed) within a few hours in the reference system when NO 3 − concentrations were 1.3–1.8 μmol/L. In contrast, only 50–60% of incoming NO 3 − was processed in the fertilized system when NO 3 − concentrations were 84–96 μmol/L; the remainder was exported in ebb tidewater. Gross NO 3 − processing was ∼40 times higher in the fertilized system at 19.34–24.67 mol NO 3 ‐N·ha −1 ·h −1 . Dissimilatory nitrate reduction to ammonium was evident in both systems during the first 48 h of the tracer additions but 15 NO 3 − was exported as 15 NH 4 + . Nitrification rates calculated by 15 NO 3 − dilution were 6.05 and 4.46 mol·ha −1 ·h −1 in the fertilized system but could not be accurately calculated in the reference system due to rapid ( 3 − turnover. Over the five‐day paired tracer addition, sediments sequestered a small fraction of incoming NO 3 − , although the efficiency of sequestration was 3.8% in the reference system and 0.7% in the fertilized system. Gross sediment N sequestration rates were similar at 13.5 and 12.6 mol·ha −1 ·d −1 , respectively. Macrophyte NO 3 − uptake efficiency, based on tracer incorporation in aboveground tissues, was considerably higher in the reference system (16.8%) than the fertilized system (2.6%), although bulk uptake of NO 3 − by plants was lower in the reference system (1.75 mol NO 3 − ·ha −1 ·d −1 ) than the fertilized system (∼10 mol NO 3 − ·ha −1 ·d −1 ). Nitrogen processing efficiency decreased with NO 3 − load in all pools, suggesting that the nutrient processing capacity of the marsh ecosystem was exceeded in the fertilized marsh.

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Tiny Stowaways: Analyzing the Economic Benefits of a U.S. Environmental Protection Agency Permit Regulating Ballast Water Discharges - Sabrina J. Lovell; Lisa A. Drake (Environmental Management, 2009)

Disturbance, rainfall and contrasting species responses mediated aboveground biomass response to 11 years of CO 2 enrichment in a Florida scrub‐oak ecosystem - TROY J. SEILER; DANIEL P. RASSE; JIAHONG LI; PAUL DIJKSTRA; HANS P. ANDERSON; DAVID P. JOHNSON; THOMAS L. POWELL; BRUCE A. HUNGATE; C. ROSS HINKLE; BERT G. DRAKE (Global Change Biology, 2009)
This study reports the aboveground biomass response of a fire‐regenerated Florida scrub‐oak ecosystem exposed to elevated CO 2 (1996–2007), from emergence after fire through canopy closure. Eleven years exposure to elevated CO 2 caused a 67% increase in aboveground shoot biomass. Growth stimulation was sustained throughout the experiment; although there was significant variability between years. The absolute stimulation of aboveground biomass generally declined over time, reflecting increasing environmental limitations to long‐term growth response. Extensive defoliation caused by hurricanes in September 2004 was followed by a strong increase in shoot density in 2005 that may have resulted from reopening the canopy and relocating nitrogen from leaves to the nutrient‐poor soil. Biomass response to elevated CO 2 was driven primarily by stimulation of growth of the dominant species, Quercus myrtifolia , while Quercus geminata , the other co‐dominant oak, displayed no significant CO 2 response. Aboveground growth also displayed interannual variation, which was correlated with total annual rainfall. The rainfall × CO 2 interaction was partially masked at the community level by species‐specific responses: elevated CO 2 had an ameliorating effect on Q. myrtifolia growth under water stress. The results of this long‐term study not only show that atmospheric CO 2 concentration had a consistent stimulating effect on aboveground biomass production, but also showed that available water is the primary driver of interannual variation in shoot growth and that the long‐term response to elevated CO 2 may have been caused by other factors such as nutrient limitation and disturbance.

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

Functional Richness and Relative Resilience of Bird Communities in Regions with Different Land Use Intensities - J. Fischer; D. B. Lindenmayer; S. P. Blomberg; R. Montague-Drake; A. Felton; J. A. Stein (Ecosystems, 2007)

An oxygen‐mediated positive feedback between elevated carbon dioxide and soil organic matter decomposition in a simulated anaerobic wetland - AMELIA A. WOLF; BERT G. DRAKE; JOHN E. ERICKSON; J. PATRICK MEGONIGAL (Global Change Biology, 2007)
We examined the effects of elevated atmospheric CO 2 on soil carbon decomposition in an experimental anaerobic wetland system. Pots containing either bare C 4 ‐derived soil or the C 3 sedge Scirpus olneyi planted in C 4 ‐derived soil were incubated in greenhouse chambers at either ambient or twice‐ambient atmospheric CO 2 . We measured CO 2 flux from each pot, quantified soil organic matter (SOM) mineralization using δ 13 C, and determined root and shoot biomass. SOM mineralization increased in response to elevated CO 2 by 83–218% ( P P = 0.003). Our results (1) show that there is a positive feedback between elevated atmospheric CO 2 concentrations and wetland SOM decomposition and (2) suggest that this process is mediated by the release of oxygen from the roots of wetland plants. Because this feedback may occur in any wetland system, including peatlands, these results suggest a limitation on the size of the carbon sink presented by anaerobic wetland soils in a future elevated‐CO 2 atmosphere.

Effects of the river discharge management on the nursery function of the Guadalquivir river estuary (SW Spain) - Carlos Fernández-Delgado; F. Baldó; C. Vilas; D. García-González; J. A. Cuesta; E. González-Ortegón; P. Drake (Hydrobiologia, 2007)

Weighted gene coexpression network analysis strategies applied to mouse weight - Tova F. Fuller; Anatole Ghazalpour; Jason E. Aten; Thomas A. Drake; Aldons J. Lusis; Steve Horvath (Mammalian Genome, 2007)

Production of Landsat ETM+ reference imagery of burned areas within Southern African savannahs: comparison of methods and application to MODIS - A. M. S. Smith; N. A. Drake; M. J. Wooster; A. T. Hudak; Z. A. Holden; C. J. Gibbons (International Journal of Remote Sensing, 2007)

Impacts of Hurricane Frances on Florida scrub‐oak ecosystem processes: defoliation, net CO 2 exchange and interactions with elevated CO 2 - JIAHONG LI; THOMAS L. POWELL; TROY J. SEILER; DAVID P. JOHNSON; HANS P. ANDERSON; ROSVEL BRACHO; BRUCE A. HUNGATE; CHARLES R. HINKLE; BERT G. DRAKE (Global Change Biology, 2007)
Hurricane disturbances have profound impacts on ecosystem structure and function, yet their effects on ecosystem CO 2 exchange have not been reported. In September 2004, our research site on a fire‐regenerated scrub‐oak ecosystem in central Florida was struck by Hurricane Frances with sustained winds of 113 km h −1 and wind gusts as high as 152 km h −1 . We quantified the hurricane damage on this ecosystem resulting from defoliation: we measured net ecosystem CO 2 exchange, the damage and recovery of leaf area, and determined whether growth in elevated carbon dioxide concentration in the atmosphere ( C a ) altered this disturbance. The hurricane decreased leaf area index (LAI) by 21%, which was equal to 60% of seasonal variation in canopy growth during the previous 3 years, but stem damage was negligible. The reduction in LAI led to a 22% decline in gross primary production (GPP) and a 25% decline in ecosystem respiration ( R e ). The compensatory declines in GPP and R e resulted in no significant change in net ecosystem production (NEP). Refoliation began within a month after the hurricane, although this period was out of phase with the regular foliation period, and recovered 20% of the defoliation loss within 2.5 months. Full recovery of LAI, ecosystem CO 2 assimilation, and ecosystem respiration did not occur until the next growing season. Plants exposed to elevated C a did not sustain greater damage, nor did they recover faster than plants grown under ambient C a . Thus, our results indicate that hurricanes capable of causing significant defoliation with negligible damage to stems have negligible effects on NEP under current or future CO 2 ‐enriched environment.

Salinity and sea level mediate elevated CO 2 effects on C 3 –C 4 plant interactions and tissue nitrogen in a Chesapeake Bay tidal wetland - JOHN E. ERICKSON; J. PATRICK MEGONIGAL; GARY PERESTA; BERT G. DRAKE (Global Change Biology, 2007)
Elevated atmospheric carbon dioxide concentrations ([CO 2 ]) generally increase plant photosynthesis in C 3 species, but not in C 4 species, and reduce stomatal conductance in both C 3 and C 4 plants. In addition, tissue nitrogen concentration ([N]) often fails to keep pace with enhanced carbon gain under elevated CO 2 , particularly in C 3 species. While these responses are well documented in many species, implications for plant growth and nutrient cycling in native ecosystems are not clear. Here we present data on 18 years of measurement of above and belowground biomass, tissue [N] and total standing crop of N for a Scirpus olneyi ‐dominated (C 3 sedge) community, a Spartina patens ‐dominated (C 4 grass) community and a C 3 –C 4 ‐mixed species community exposed to ambient and elevated (ambient +340 ppm) atmospheric [CO 2 ] in natural salinity and sea level conditions of a Chesapeake Bay wetland. Increased biomass production (shoots plus roots) under elevated [CO 2 ] in the S. olneyi ‐dominated community was sustained throughout the study, averaging approximately 35%, while no significant effect of elevated [CO 2 ] was found for total biomass in the C 4 ‐dominated community. We found a significant decline in C 4 biomass (correlated with rising sea level) and a concomitant increase in C 3 biomass in the mixed community. This shift from C 4 to C 3 was accelerated by the elevated [CO 2 ] treatment. The elevated [CO 2 ] stimulation of total biomass accumulation was greatest during rainy, low salinity years: the average increase above the ambient treatment during the three wettest years (1994, 1996, 2003) was 2.9 t ha −1 but in the three driest years (1995, 1999, 2002), it was 1.2 t ha −1 . Elevated [CO 2 ] depressed tissue [N] in both species, but especially in the S. olneyi where the relative depression was positively correlated with salinity and negatively related with the relative enhancement of total biomass production. Thus, the greatest amount of carbon was added to the S. olneyi ‐dominated community during years when shoot [N] was reduced the most, suggesting that the availability of N was not the most or even the main limitation to elevated [CO 2 ] stimulation of carbon accumulation in this ecosystem.

Integrating genetic and gene expression data: application to cardiovascular and metabolic traits in mice - Thomas A. Drake; Eric E. Schadt; Aldons J. Lusis (Mammalian Genome, 2006)

Rapid root closure after fire limits fine root responses to elevated atmospheric CO 2 in a scrub oak ecosystem in central Florida, USA - FRANK P. DAY; DANIEL B. STOVER; ALISHA L. PAGEL; BRUCE A. HUNGATE; JOHN J. DILUSTRO; BRANDON T. HERBERT; BERT G. DRAKE; CHARLES R. HINKLE (Global Change Biology, 2006)
Elevated atmospheric carbon dioxide (CO 2 ) often stimulates the growth of fine roots, yet there are few reports of responses of intact root systems to long‐term CO 2 exposure. We investigated the effects of elevated CO 2 on fine root growth using open top chambers in a scrub oak ecosystem at Kennedy Space Center, Florida for more than 7 years. CO 2 enrichment began immediately after a controlled burn, which simulated the natural disturbance that occurs in this system every 10–15 years. We hypothesized that (1) root abundance would increase in both treatments as the system recovered from fire; (2) elevated CO 2 would stimulate root growth; and (3) elevated CO 2 would alter root distribution. Minirhizotron tubes were used to measure fine root length density (mm cm −2 ) every three months. During the first 2 years after fire recovery, fine root abundance increased in all treatments and elevated CO 2 significantly enhanced root abundance, causing a maximum stimulation of 181% after 20 months. The CO 2 stimulation was initially more pronounced in the top 10 cm and 38–49 cm below the soil surface. However, these responses completely disappeared during the third year of experimental treatment: elevated CO 2 had no effect on root abundance or on the depth distribution of fine roots during years 3–7. The results suggest that, within a few years following fire, fine roots in this scrub oak ecosystem reach closure, defined here as a dynamic equilibrium between production and mortality. These results further suggest that elevated CO 2 hastens root closure but does not affect maximum root abundance. Limitation of fine root growth by belowground resources – particularly nutrients in this nutrient‐poor soil – may explain the transient response to elevated CO 2 .

Discrete-trials heroin self-administration produces sensitization to the reinforcing effects of cocaine in rats - Sara J. Ward; Christopher Läck; Drake Morgan; David C. S. Roberts (Psychopharmacology, 2006)

The Decapod Custacean Community of the Guadalquivir Estuary (SW Spain): Seasonal and Inter-Year Changes in Community Structure - J. A. Cuesta; E. González-Ortegón; A. Rodríguez; F. Baldó; C. Vilas; P. Drake (Hydrobiologia, 2006)

A case for informed consent? Indoor UV tanning facility operator’s provision of health risks information (United States) - Lauren F. Heilig; Renee D’Ambrosia; Amanda L. Drake; Robert P. Dellavalle; Eric J. Hester (Cancer Causes & Control, 2005)

Factors associated with time to availability for cases reported to population-based cancer registries⋆ - Julie Smith-Gagen; Rosemary D. Cress; Christiana M. Drake; Martha C. Felter; James J. Beaumont (Cancer Causes & Control, 2005)

Comparative Aquatic Toxicity Evaluation of 2-(Thiocyanomethylthio)benzothiazole and Selected Degradation Products Using Ceriodaphnia dubia - S. T. Nawrocki; K. D. Drake; C. F. Watson; G. D. Foster; K. J. Maier (Archives of Environmental Contamination and Toxicology, 2005)

Vector projection of biomagnetic fields - L. A. Bradshaw; A. Myers; W. O. Richards; W. Drake; J. P. Wikswo (Medical & Biological Engineering & Computing, 2005)

Invasion in space and time: non‐native species richness and relative abundance respond to interannual variation in productivity and diversity - Elsa E. Cleland; Melinda D. Smith; Sandy J. Andelman; Christy Bowles; Karen M. Carney; M. Claire Horner‐Devine; John M. Drake; Sarah M. Emery; Joel M. Gramling; David B. Vandermast (Ecology Letters, 2004)
Ecologists have long sought to understand the relationships among species diversity, community productivity and invasion by non‐native species. Here, four long‐term observational datasets were analyzed using repeated measures statistics to determine how plant species richness and community resource capture (i.e. productivity) influenced invasion. Multiple factors influenced the results, including the metric used to quantify invasion, interannual variation and spatial scale. Native richness was positively correlated with non‐native richness, but was usually negatively correlated with non‐native abundance, and these patterns were stronger at the larger spatial scale. Logistic regressions indicated that the probability of invasion was reduced both within and following years with high productivity, except at the desert grassland site where high productivity was associated with increased invasion. Our analysis suggests that while non‐natives were most likely to establish in species rich communities, their success was diminished by high resource capture by the resident community.

The use of reference strand‐mediated conformational analysis for the study of cheetah ( Acinonyx jubatus ) feline leucocyte antigen class II DRB polymorphisms - G. J. C. Drake; L. J. Kennedy; H. K. Auty; R. Ryvar; W. E. R. Ollier; A. C. Kitchener; A. R. Freeman; A. D. Radford (Molecular Ecology, 2004)
There is now considerable evidence to suggest the cheetah ( Acinonyx jubatus ) has limited genetic diversity. However, the extent of this and its significance to the fitness of the cheetah population, both in the wild and captivity, is the subject of some debate. This reflects the difficulty associated with establishing a direct link between low variability at biologically significant loci and deleterious aspects of phenotype in this, and other, species. Attempts to study one such region, the feline leucocyte antigen (FLA), are hampered by a general reliance on cloning and sequencing which is expensive, labour‐intensive, subject to PCR artefact and always likely to underestimate true variability. In this study we have applied reference strand‐mediated conformational analysis (RSCA) to determine the FLA–DRB phenotypes of 25 cheetahs. This technique was rapid, repeatable and less prone to polymerase chain reaction (PCR)‐induced sequence artefacts associated with cloning. Individual cheetahs were shown to have up to three FLA–DRB genes. A total of five alleles were identified (DRB*ha14–17 and DRB*gd01) distributed among four genotypes. Fifteen cheetahs were DRB*ha14/ha15/ha16/ha17, three were DRB*ha15/ha16/ha17, six were DRB*ha14/ha16/ha17 and one was DRB*ha14/ha15/ha16/ha17/gd01. Sequence analysis of DRB*gd01 suggested it was a recombinant of DRB*ha16 and DRB*ha17. Generation of new alleles is difficult to document, and the clear demonstration of such an event is unusual. This study confirms further the limited genetic variability of the cheetah at a biologically significant region. RSCA will facilitate large‐scale studies that will be needed to correlate genetic diversity at such loci with population fitness in the cheetah and other species.

Effects of elevated atmospheric CO 2 on net ecosystem CO 2 exchange of a scrub–oak ecosystem - Graham J. Hymus; David P. Johnson; Sabina Dore; Hans P. Anderson; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2003)
We report the results of a 2‐year study of effects of the elevated (current ambient plus 350 μmol CO 2 mol −1 ) atmospheric CO 2 concentration ( C a ) on net ecosystem CO 2 exchange ( NEE ) of a scrub–oak ecosystem. The measurements were made in open‐top chambers (OTCs) modified to function as open gas‐exchange systems. The OTCs enclosed samples of the ecosystem (ca. 10 m 2 surface area) that had regenerated after a fire, 5 years before, in either current ambient or elevated C a . Throughout the study, elevated C a increased maximum NEE ( NEE max ) and the apparent quantum yield of the NEE ( φ NEE ) during the photoperiod. The magnitude of the stimulation of NEE max , expressed per unit ground area, was seasonal, rising from 50% in the winter to 180% in the summer. The key to this stimulation was effects of elevated C a , and their interaction with the seasonal changes in the environment, on ecosystem leaf area index, photosynthesis and respiration. The separation of these factors was difficult. When expressed per unit leaf area the stimulation of the NEE max ranged from 7% to 60%, with the increase being dependent on increasing soil water content ( W soil ). At night, the CO 2 effluxes from the ecosystem ( NEE night ) were on an average 39% higher in elevated C a . However, the increase varied between 6% and 64%, and had no clear seasonality. The partitioning of NEE night into its belowground ( R below ) and aboveground ( R above ) components was carried out in the winter only. A 35% and 27% stimulation of NEE night in December 1999 and 2000, respectively, was largely due to a 26% and 28% stimulation of R below in the respective periods, because R below constituted ca. 87% of NEE night . The 37% and 42% stimulation of R above in December 1999 and 2000, respectively, was less than the 65% and 80% stimulation of the aboveground biomass by elevated C a at these times. An increase in the relative amount of the aboveground biomass in woody tissue, combined with a decrease in the specific rate of stem respiration of the dominant species Quercus myrtifolia in elevated C a , was responsible for this effect. Throughout this study, elevated C a had a greater effect on carbon uptake than on carbon loss, in terms of both the absolute flux and relative stimulation. Consequently, for this scrub–oak ecosystem carbon sequestration was greater in the elevated C a during this 2‐year study period.

Water resource partitioning, stem xylem hydraulic properties, and plant water use strategies in a seasonally dry riparian tropical rainforest - P. L. Drake; P. J. Franks (Oecologia, 2003)

The role of sFRP4, a secreted frizzled-related protein, in ovulation - J. M. Drake; R. R. Friis; A. M. Dharmarajan (Apoptosis, 2003)

Genetic loci for diet-induced atherosclerotic lesions and plasma lipids in mice - Veronica V. Colinayo; Jian-Hua Qiao; Xuping Wang; Kelly L. Krass; Eric Schadt; Aldons J. Lusis; Thomas A. Drake (Mammalian Genome, 2003)

Rhizosecretion of a monoclonal antibody protein complex from transgenic tobacco roots - Pascal M.W. Drake; Daniel M. Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Patricia Obregon; Julian K-C. Ma (Plant Molecular Biology, 2003)

Above‐ground biomass estimation in closed canopy Neotropical forests using lidar remote sensing: factors affecting the generality of relationships - Jason B. Drake; Robert G. Knox; Ralph O. Dubayah; David B. Clark; Richard Condit; J. Bryan Blair; Michelle Hofton (Global Ecology and Biogeography, 2003)
Aim Previous studies have developed strong, site‐specific relationships between canopy metrics from lidar (light detecting and ranging) remote sensing data and forest structural characteristics such as above‐ground biomass (AGBM), but the generality of these relationships is unknown. In this study, we examine the generality of relationships between lidar metrics and forest structural characteristics, including AGBM, from two study areas in Central America with different precipitation patterns. Location A series of tropical moist forest sites in Panama and a tropical wet forest in Costa Rica. Methods Canopy metrics (e.g. canopy height) were calculated from airborne lidar data. Basal area, mean stem diameter and AGBM were calculated from measurements taken as a part of ongoing forest dynamics studies in both areas. We examined the generality of relationship between lidar metrics and forest structure, and possible environmental effects (e.g. leaf phenology). Results We found that lidar metrics were strongly correlated ( R 2 : 0.65–0.92) with mean stem diameter, basal area and AGBM in both regions. We also show that the relationships differed between these regions. Deciduousness of canopy trees in the tropical moist forest area accounted for the differences in predictive equations for stem diameter and basal area. The relationships between lidar metrics and AGBM, however, remained significantly different between the two study areas even after adjusting for leaf drop. We attribute this to significant differences in the underlying allometric relationships between stem diameter and AGBM in tropical wet and moist forests. Conclusions Important forest structural characteristics can be estimated reliably across a variety of conditions sampled in these closed‐canopy tropical forests. Environmental factors such as drought deciduousness have an important influence on these relationships. Future efforts should continue to examine climatic factors that may influence the generality of the relationships between lidar metrics and forest structural characteristics and assess more rigorously the generality of field‐derived allometric relationships.

The clonal structure of Quercus geminata revealed by conserved microsatellite loci - E. A. Ainsworth; P. J. Tranel; B. G. Drake; S. P. Long (Molecular Ecology, 2003)
The scrub oak communities of the southeastern USA may have existed at their present locations for thousands of years. These oaks form suckers, and excavations of root systems suggest that clones may occupy very large areas. Resolution of the clonal nature of scrub oaks is important both to manage the tracts of this ecosystem that remain, and in conducting long‐term ecological studies, where the study area must substantially exceed the area occupied by any single clone. Microsatellites were used to determine the genetic diversity of a dominant oak species within a 2‐ha long‐term experimental site on Merritt Island at the Kennedy Space Center. This area contains a long‐term study of the effects of elevated CO 2 on the ecosystem. Conservation of seven microsatellite loci, previously identified in the sessile oak, Quercus petraea , was tested in two Florida scrub oak species, Q. geminata and Q. myrtifolia . Sequence analysis revealed that all seven microsatellite loci were conserved in Q. geminata and five loci were conserved in Q. myrtifolia . Six microsatellite loci were polymorphic in Q. geminata and these were subsequently used to investigate the clonal structure of the Q. geminata population. Twenty‐one unique combinations of microsatellites, or haplotypes, occurred only once, whereas the remaining 26 individuals belonged to a total of seven different haplotypes. Trees with identical haplotypes were in close proximity, supporting the interpretation that they were clones. The results showed that there is significant genetic diversity within the 2‐ha experimental site. Microsatellites provided a powerful and noninvasive tool for distinguishing individual genotypes and determining an adequate area for long‐term ecosystem studies.

Cross validation of open‐top chamber and eddy covariance measurements of ecosystem CO 2 exchange in a Florida scrub‐oak ecosystem - Sabina Dore; Graham J. Hymus; David P. Johnson; C. R. Hinkle; Riccardo Valentini; Bert G. Drake (Global Change Biology, 2003)
Simultaneous measurements of net ecosystem CO 2 exchange (NEE) were made in a Florida scrub‐oak ecosystem in August 1997 and then every month between April 2000 to July 2001, using open top chambers (NEE O ) and eddy covariance (NEE E ). This study provided a cross validation of these two different techniques for measuring NEE. Unique characteristics of the comparison were that the measurements were made simultaneously, in the same stand, with large replicated chambers enclosing a representative portion of the ecosystem (75 m 2 , compared to approximately 1–2 ha measured by the eddy covariance system). The value of the comparison was greatest at night, when the microclimate was minimally affected by the chambers. For six of the 12 measurement periods, night NEE O was not significantly different to night NEE E , and for the other periods the maximum difference was 1.1 µ mol m − 2 s − 1 , with an average of 0.72 ± 0.09 µ mol m − 2 s − 1 . The comparison was more difficult during the photoperiod, because of differences between the microclimate inside and outside the chambers. During the photoperiod, air temperature (T air ) and air vapour pressure deficits (VPD) became progressively higher inside the chambers until mid‐afternoon. In the morning NEE O was higher than NEE E by about 26%, consistent with increased temperature inside the chambers. Over the mid‐day period and the afternoon, NEE O was 8% higher that NEE E , regardless of the large differences in microclimate. This study demonstrates both the uses and difficulties associated with attempting to cross validate NEE measurements made in chambers and using eddy covariance. The exercise was most useful at night when the chamber had a minimal effect on microclimate, and when the measurement of NEE is most difficult.

Direct and indirect effects of elevated CO 2 on transpiration from Quercus myrtifolia in a scrub‐oak ecosystem - J.‐H. Li; W. A. Dugas; G. J. Hymus; D. P. Johnson; C. R. Hinkle; B. G. Drake; B. A. Hungate (Global Change Biology, 2003)
Elevated atmospheric carbon dioxide (C a ) usually reduces stomatal conductance, but the effects on plant transpiration in the field are not well understood. Using constant‐power sap flow gauges, we measured transpiration from Quercus myrtifolia Willd., the dominant species of the Florida scrub‐oak ecosystem, which had been exposed in situ to elevated C a (350 µmol mol − 1 above ambient) in open‐top chambers since May 1996. Elevated C a reduced average transpiration per unit leaf area by 37%, 48% and 49% in March, May and October 2000, respectively. Temporarily reversing the C a treatments showed that at least part of the reduction in transpiration was an immediate, reversible response to elevated C a . However, there was also an apparent indirect effect of C a on transpiration: when transpiration in all plants was measured under common C a , transpiration in elevated C a ‐grown plants was lower than that in plants grown in normal ambient C a . Results from measurements of stomatal conductance (g s ), leaf area index (LAI), canopy light interception and correlation between light and g s indicated that the direct, reversible C a effect on transpiration was due to changes in g s caused by C a , and the indirect effect was caused mainly by greater self‐shading resulting from enhanced LAI, not from stomatal acclimation. By reducing light penetration through the canopy, the enhanced self‐shading at elevated C a decreased stomatal conductance and transpiration of leaves at the middle and bottom of canopy. This self‐shading mechanism is likely to be important in ecosystems where LAI increases in response to elevated C a .

Seasonal variability in the effect of elevated CO 2 on ecosystem leaf area index in a scrub‐oak ecosystem - Graham J. Hymus; Jean‐Yves Pontailler; Jiahong Li; Peter Stiling; C. Ross Hinkle; Bert G. Drake (Global Change Biology, 2002)
We report effects of elevated atmospheric CO 2 concentration ( C a ) on leaf area index (LAI) of a Florida scrub‐oak ecosystem, which had regenerated after fire for between three and five years in open‐top chambers (OTCs) and was yet to reach canopy closure. LAI was measured using four nondestructive methods, calibrated and tested in experiments performed in calibration plots near the OTCs. The four methods were: PAR transmission through the canopy, normalized difference vegetation index (NDVI), hemispherical photography, and allometric relationships between plant stem diameter and plant leaf area. Calibration experiments showed: (1) Leaf area index could be accurately determined from either PAR transmission through the canopy or hemispherical photography. For LAI determined from PAR transmission through the canopy, ecosystem light extinction coefficient ( k ) varied with season and was best described as a function of PAR transmission through the canopy. (2) A negative exponential function described the relationship between NDVI and LAI; (3) Allometric relationships overestimated LAI. Throughout the two years of this study, LAI was always higher in elevated C a , rising from, 20% during winter, to 55% during summer. This seasonality was driven by a more rapid development of leaf area during the spring and a relatively greater loss of leaf area during the winter, in elevated C a . For this scrub‐oak ecosystem prior to canopy closure, increased leaf area was an indirect mechanism by which ecosystem C uptake and canopy N content were increased in elevated C a . In addition, increased LAI decreased potential reductions in canopy transpiration from decreases in stomatal conductance in elevated C a . These findings have important implications for biogeochemical cycles of C, N and H 2 O in woody ecosystems regenerating from disturbance in elevated C a .

Genetic characterization of the Dyscalc locus - Veronica V. Colinayo; Jian-Hua Qiao; Peter Demant; Kelly Krass; Aldons J. Lusis; Thomas A. Drake (Mammalian Genome, 2002)

Extensive belowground carbon storage supports roots and mycorrhizae in regenerating scrub oaks - J. Langley; B. Drake; B. Hungate (Oecologia, 2002)

Potential disruptions to seed dispersal mutualisms in Tonga, Western Polynesia - Hayley J. Meehan; Kim R. McConkey; Donald R. Drake (Journal of Biogeography, 2002)
Aim As a result of the extinctions of several large frugivorous birds (and one flying fox) and the diminished ranges of others, Tonga now has a relatively small number of effective seed dispersers, especially for large‐seeded plants. We estimate the bill width and gape of the two largest known extinct pigeon species ( Ducula ) present in Tonga prior to human arrival. We then estimate which native rain forest species had fruits that would have probably been included in the diets of these extinct birds but which may not be dispersed regularly by the smaller frugivores present today. Methods Bill width for the two largest extinct pigeons was derived by extrapolating from the size of fossil bones and measurements of skeletons of extant Ducula species. Ducula and Ptilinopus species have distensible jaws, and therefore their gape allows them to swallow objects broader than their bill width. We estimated the gape width and maximum ingestible fruit size that both the extinct and extant species could consume, by extrapolating from feeding observations of extant Ducula and Ptilinopus species (using known bill widths and fruit sizes). We determined whether those plant species whose fruit diameters exceed the mean gape width of the largest remaining avian frugivore in Tonga ( Ducula pacifica Gmelin) appeared adapted for dispersal by birds or flying foxes. Results Approximately 79% of the native rain forest trees and lianas in Tonga produce fruits whose morphology suggests that they are adapted to vertebrate dispersal. Bill width estimates derived from the bones of the extinct Ducula sp. nova suggest that this pigeon could swallow fruit up to 48 mm in diameter, whilst the smaller Ducula cf. david Balouet & Olson is estimated to have been able to swallow fruit up to 36 mm in diameter. Plant species whose fruits are too large to be swallowed by Tonga's largest extant frugivorous bird ( D. pacifica ) yet display fruit characteristics suggesting birds were likely to have been their predominant vertebrate disperser in pre‐human times include: Calophyllum inophyllum L. , Cerbera odollam Gaertn, Planchonella garberi Christophersen , P. membranacea Lam. , Pometia pinnata J. R. & G. Forst., Syzygium quandrangulatum (A. Gray) Merr. & Perry , Syzygium richii (A. Gray) Merr. & Perry and Terminalia catappa L. Main conclusions There is now no avian disperser in Tonga for plant species whose fruits measure >28 mm in diameter (the maximum gape of D. pacifica ). Although frugivorous flying foxes ( Pteropus tonganus Quoy & Gaimard) may eat the fruit and disperse the seeds of the eight plant species identified with large fruits, the frequency of dispersal by birds was probably much higher in the past. Species that once relied on the large extinct pigeons for dispersal may have become reduced in abundance in their absence.

Acclimation of photosynthesis and respiration to elevated atmospheric CO 2 in two Scrub Oaks - Graham J. Hymus; Tom G. Snead; David P. Johnson; Bruce A. Hungate; Bert G. Drake (Global Change Biology, 2002)
For two species of oak, we determined whether increasing atmospheric CO 2 concentration ( C a ) would decrease leaf mitochondrial respiration (R) directly, or indirectly owing to their growth in elevated C a , or both. In particular, we tested whether acclimatory decreases in leaf‐Rubisco content in elevated C a would decrease R associated with its maintenance. This hypothesis was tested in summer 2000 on sun and shade leaves of Quercus myrtifolia Willd. and Quercus geminata Small. We also measured R on five occasions between summer 1999 and 2000 on leaves of Q. myrtifolia . The oaks were grown in the field for 4 years, in either current ambient or elevated (current ambient + 350 µmol mol −1 ) C a , in open‐top chambers (OTCs). For Q. myrtifolia , an increase in C a from 360 to 710 µmol mol −1 had no direct effect on R at any time during the year. In April 1999, R in young Q. myrtifolia leaves was significantly higher in elevated C a —the only evidence for an indirect effect of growth in elevated C a . Leaf R was significantly correlated with leaf nitrogen (N) concentration for the sun and shade leaves of both the species of oak. Acclimation of photosynthesis in elevated C a significantly reduced maximum RuBP‐saturated carboxylation capacity ( V c max ) for both the sun and shade leaves of only Q. geminata . However, we estimated that only 11–12% of total leaf N was invested in Rubisco; consequently, acclimation in this plant resulted in a small effect on N and an insignificant effect on R. In this study measurements of respiration and photosynthesis were made on material removed from the field; this procedure had no effect on gas exchange properties. The findings of this study were applicable to R expressed either per unit leaf area or unit dry weight, and did not support the hypothesis that elevated C a decreases R directly, or indirectly owing to acclimatory decreases in Rubisco content.

Evapotranspiration and soil water content in a scrub‐oak woodland under carbon dioxide enrichment - B. A. Hungate; M. Reichstein; P. Dijkstra; D. Johnson; G. Hymus; J. D. Tenhunen; C.R. Hinkle; B. G. Drake (Global Change Biology, 2002)
Leaf conductance often decreases in response to elevated atmospheric CO 2 concentration ( C a ) potentially leading to changes in hydrology. We describe the hydrological responses of Florida scrub oak to elevated C a during an eight‐month period two years after C a manipulation began. Whole‐chamber gas exchange measurements revealed a consistent reduction in evapotranspiration in response to elevated C a , despite an increase in leaf area index (LAI). Elevated C a also increased surface soil water content, but xylem water deuterium measurements show that the dominant oaks in this system take up most of their water from the water table (which occurs at a depth of 1.5–3 m), suggesting that the water savings in elevated C a in this system are primarily manifested as reduced water uptake at depth. Extrapolating these results to larger areas requires considering a number of processes that operate on scales beyond these accessible in this field experiment. Nevertheless, these results demonstrate the potential for reduced evapotranspiration and associated changes in hydrology in ecosystems dominated by woody vegetation in response to elevated C a .

Effects of elevated atmospheric CO 2 on root decomposition in a scrub oak ecosystem - John J. Dilustro; Frank P. Day; Bert G. Drake (Global Change Biology, 2001)
The effects of elevated atmospheric CO 2 on fine root decomposition over a 828‐day period were investigated using open top chambers with both ambient and elevated (700 ppm) CO 2 treatments in an oak–palmetto scrub ecosystem at Kennedy Space Center, Florida. Carbon dioxide enrichment of the chambers began 15 May 1996. The experiment included roots grown in ambient and elevated carbon dioxide. Vertical litterbags installed in September 1996 in each elevated and ambient chamber incubated from December 1996 to December 1998 showed no significant treatment effect on fine root or rhizome mass loss. Initial fine root percentage mass loss varied from 10.3% to 13.5% after three months; 55.5% to 38.3% of original mass had been lost after 828 days. A period of nitrogen immobilization occurred in both fine roots and rhizomes in the elevated CO 2 incubation, which is a potential mechanism for nitrogen conservation for this system in an elevated CO 2 world .

An Evaluation of Restoration Efforts in Fishless Lakes Stocked with Exotic Trout - Deanne C. Drake; Robert J. Naiman (Conservation Biology, 2000)
Detrimental effects of introduced fishes on native amphibian populations have prompted removal of introduced cutthroat ( Oncorhynchus clarki ), rainbow ( Oncorhynchus mykiss ), and brook trout ( Salvelinus fontinalis ) from naturally fishless lakes at Mt. Rainier National Park, Washington ( U.S.A.). Using paleolimnological indicators (diatoms, invertebrates, and sediment characteristics) in eight 480‐year‐old sediment cores from eight lakes, we (1) derived estimates of baseline environmental conditions and natural variation, (2) assessed the effects of stocking naturally fishless lakes, and (3) determined whether lakes returned to predisturbance conditions after fish removal (restoration). Diatom floras were relatively stable between 315 and 90 years before present in all lakes; we used this time period to define lake‐specific “baseline” conditions. Dissimilarity analyses of diatoms revealed sustained, dramatic changes in diatom floras that occurred approximately 80 years ago (when fish were introduced) in four of five stocked lakes, whereas the diatom floras in two unstocked lakes had not changed significantly in the last 315 years. Diatoms were not preserved in an eighth lake. State changes also occurred in two lakes over 200 years before European settlement of the Pacific Northwest. Preserved invertebrate densities fluctuated dramatically over time in all cores, providing a poor reference for assessing the effects of fishes. Nevertheless, fish‐invertebrate interactions have been demonstrated in other paleolimnological studies and may be useful for lower‐elevation or more productive lakes. Because diatom communities have not returned to predisturbance assemblages in restored lakes, even 20–30 years after fish removal, we conclude that Mt. Rainier lakes were not successfully restored by the removal of fishes.

An Evaluation of Restoration Efforts in Fishless Lakes Stocked with Exotic Trout - Deanne C. Drake; Robert J. Naiman (Conservation Biology, 2000)

Leaf senescence of Quercus myrtifolia as affected by long‐term CO 2 enrichment in its native environment - J. ‐H. Li; P. Dijkstra; G. J. Hymus; R. M. Wheeler; W. C. Piastuch; C. R. Hinkle; B. G. Drake (Global Change Biology, 2000)
Summary The long‐term effects of elevated (ambient plus 350 μmol mol −1 ) atmospheric CO 2 concentration (C a ) on the leaf senescence of Quercus myrtifolia Willd was studied in a scrub‐oak community during the transition from autumn (December 1997) to spring (April 1998). Plants were grown in large open‐top chambers at the Smithsonian CO 2 Research Site, Merritt Island Wildlife Refuge, Cape Canaveral, Florida. Chlorophyll (a + b) concentration, Rubisco activity and N concentration decreased by 75%, 82%, and 52%, respectively, from December (1997) to April (1998) in the leaves grown at ambient C a . In contrast, the leaves of plants grown at elevated C a showed no significant decrease in chlorophyll (a + b) concentration or Rubisco activity, and only a 25% reduction in nitrogen. These results indicate that leaf senescence was delayed during this period at elevated C a . Delayed leaf senescence in elevated C a had important consequences for leaf photosynthesis. In elevated C a the net photosynthetic rate of leaves that flushed in Spring 1997 (last year's leaves) and were 13 months old was not different from fully‐expanded leaves that flushed in 1998, and were approximately 1 month old (current year's leaves). In ambient C a the net photosynthetic rate of last year's leaves was 54% lower than for current year's leaves. When leaves were fully senesced, nitrogen concentration decreased to about 40% of the concentration in non‐senesced leaves, in both CO 2 treatments. In April, net photosynthesis was 97% greater in leaves grown in elevated C a than in those grown at ambient. During the period when elevated C a delayed leaf senescence, more leaves operating at higher photosynthetic rate would allow the ecosystem dominated by Q. myrtifolia to gain more carbon at elevated C a than at ambient C a .

A murine monoclonal antibody produced in transgenic plants with plant-specific glycans is not immunogenic in mice - Daniel Chargelegue; Nicholas D. Vine; Craig J. van Dolleweerd; Pascal M.W. Drake; Julian K-C. Ma (Transgenic Research, 2000)

Depletion of endogenous dopamine stores and shift in β-adrenoceptor subtypes in cardiac tissue following five weeks of chronic denervation - Ger J. Van der Vusse; Marie-Louise Dubelaar; Will A. Coumans; Markus Steinfath; Chris C.T. Smith; Angela J. Drake-Holland; Mark I.M. Noble (Molecular and Cellular Biochemistry, 1998)

Effects of copper-contaminated sediments on Hyalella azteca, Daphnia magna, and Ceriodaphnia dubia: Survival, growth, and enzyme inhibition - J. A. Kubitz; E. C. Lewek; J. M. Besser; J. B. Drake; J. P. Giesy (Archives of Environmental Contamination and Toxicology, 1995)